Integrated modelling reveals widespread distribution of invasive wild pigs across Australia - Matthew W. Rees; David J. Mitchell; Katherina Ng; Sandra K. Parsons; Kirstin M. Proft; Scott D. Foster; David Peel; Zachary Amir; Tom Bruce; Matthew S. Luskin; Jens G. Froese (Biological Conservation, 2026)

A quantitative comparison of tools for monitoring the abundance of crown-of-thorns starfish and coral cover - Emma Lawrence; Scott D. Foster; Samuel A. Matthews; David Williamson; Morgan S. Pratchett; Jason Doyle; Scott Bainbridge; Sven Uthicke; Peter C. Doll; Brano Kusy; Mohammad A. Armin; Mary C. Bonin (Coral Reefs, 2026)
Effective monitoring of crown-of-thorns starfish (COTS) populations and coral cover is critical for informing management of COTS outbreaks throughout their tropical Indo-Pacific range, including Australia’s Great Barrier Reef. However, existing monitoring tools such as manta tow and cull diver surveys have well-known limitations including accuracy and resource demands. This study evaluates a range of monitoring tools for assessing both COTS and coral populations. Tools that measure both COTS and coral include manta tow surveys, scooter-assisted large area diver-based (SALAD) surveys and surveys undertaken using the ReefScan towed camera platform. For COTS-only monitoring, we examine cull diver surveys and environmental DNA (eDNA) sampling. Data from side-by-side deployments on seven to ten reefs (depending on the tool) with varying COTS densities and coral cover were collected and analysed to calibrate estimates between tools. The calibration models developed will aid in integrating data from diverse sources and facilitate the translation of estimates based on one monitoring tool to another. Critically, the models provide a means of estimating COTS density (COTS per hectare) for monitoring tools that do not directly collect this measure, allowing more meaningful decision-making around ecological thresholds and enabling threshold-based management regardless of which tool collected the data. The study emphasises that each tool has specific applications for addressing knowledge gaps and informing management decisions, advocating for an integrated, multi-tool monitoring strategy that leverages the strengths of each tool to improve the overall effectiveness and efficiency of COTS and coral monitoring.

Murine Abdominal Aortic Aneurysm Intraluminal Thrombus Composition and Structure - Cortland H. Johns; Luke E. Schepers; Annabelle M. F. Foist; Ethan P. Foster; Anish Bedi; Niharika Narra; Claudia K. Albrecht; Abigail D. Cox; Craig J. Goergen (Annals of Biomedical Engineering, 2026)
Purpose Many abdominal aortic aneurysm (AAA) patients develop intraluminal thrombus (ILT), but the role of ILT in AAA progression and rupture is poorly understood. Methods To evaluate ILT in AAAs, we induced AAAs in C57Bl6/J mice via surgical application of topical elastase to the abdominal aorta below the renal arteries and administration of β-aminopropionitrile (BAPN) in drinking water. Ultrasound images of these AAAs were collected longitudinally over a period of 56 days to evaluate AAA growth over time. We semi-quantitatively assessed elastin degradation and inflammation from Movat’s pentachrome and H&E-stained samples, respectively. Additionally, we assessed extracellular matrix composition and elastin quality through Movat’s pentachrome stained samples. Results Mice subjected to elastase + BAPN exhibited continuous and significant AAA growth over time. Mice with ILT had more significant expansion over the length of the study ( p Conclusion Understanding the relationship between ILT formation, aortic wall degradation, and inflammation could help refine clinical strategies for monitoring and treating AAAs. These data suggest that work focused on modulating inflammation and ILT formation could offer promising pathways for non-surgical intervention in AAA treatment.

An interactive tool to identify existing evidence and research gaps on agricultural production processes to address heavy metals in foods: developed from a scoping review - Rupal Trivedi; Lauren E. O’Connor; Cassi N. Leta; Trish J. Bosse; Julie S. Davis; Arin A. Balalian; Rachel C. Thoerig; Shailesh M. Advani; Margaret J. Foster; Kyle M. Holland; David D. Baltensperger; Delbert M. Gatlin III; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Biological nanopore technology: developments and implications for the agricultural sciences - Minji Kim; Bach Pham; Joshua C. Foster; Matthew D. Moore (Trends in Food Science & Technology, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Effects of verification stage intensity and duration on $$\dot{V}O_{{2\max }}$$ determination - Andrew Foster; Erin J. Dennis; Stephanie P. Kurti; Nicholas D. Luden; Michael J. Saunders; Christopher J. Womack (European Journal of Applied Physiology, 2026)
Purpose Verification stages are recommended for maximal oxygen consumption (V̇O ₂max ) determination, but there is currently no standardization of verification stage design. We sought to determine if the length of recovery and the initial intensity of subsequent exercise influence the effectiveness of verification stages during testing for V̇O ₂max . Methods Twenty-seven participants (20 males, 7 females) completed four graded exercise tests (GXT). Each session included an identical incremental V̇O ₂max (iV̇O ₂max ) protocol, followed by one of four verification stages with combinations of short (5 min) and long (15 min) rest periods, and submaximal (one stage below maximal workload) and supramaximal (one stage above maximal workload) starting intensities. Results Although iV̇O ₂max and verification V̇O ₂max (vV̇O ₂max ) were similar across all protocols, 11–19% of participants achieved higher values during verification. About 24% of individuals who did not exhibit a V̇O ₂ plateau during the GXT exhibited a vV̇O ₂max > iV̇O ₂max in the submaximal verification protocols compared to 6–14% for the supramaximal protocols. Conclusions: Verification stages using initial submaximal intensities may increase the likelihood of achieving V̇O ₂max .

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Individual foraminiferal analysis: A promising tool for high-resolution temperature and pH reconstruction - Zifei Yang; Christopher D. Standish; Rachel M. Brown; Patrick A. Rafter; Malcolm B. Hart; Tali L. Babila; Gavin L. Foster (Chemical Geology, 2026)

Safety evaluation of a novel progesterone vaginal ring (PVR) for luteal phase support: SARA trial - Laurel A. Stadtmauer; Vicki L. Schnell; John K. Park; Cristin C. Slater; Eric D. Foster; Sarah A. Grover; Patrick W. Heiser (Drug Delivery and Translational Research, 2026)

Corrigendum to “Tracking the provenance of Greenland-sourced, Holocene aged, individual sand-sized ice-rafted debris using the Pb-isotope compositions of feldspars and 40Ar/39Ar ages of hornblendes” [Earth and Planetary Science Letters 433 (2016) 192–203] - Lee F. White; Ian Bailey; Gavin L. Foster; Georgina Allen; Simon P. Kelley; John T. Andrews; Kelly Hogan; Julian A. Dowdeswell; Craig D. Storey (Earth and Planetary Science Letters, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Ti solubility in biotite at low pressure in metapelitic systems: the Torres del Paine case - Maria M. Ariza-Acero; Lukas P. Baumgartner; C. Tom Foster; Marisa D. Acosta; Jo Moore; Jack Gillespie; Robert Bodner; Guillaume Siron (Contributions to Mineralogy and Petrology, 2026)
The Torres del Paine Intrusive Complex (TPIC) is a shallowly emplaced pluton surrounded by a well-defined contact aureole, providing an ideal setting to test Ti-in-biotite thermometry. We compare existing Ti-in-biotite thermometers with phase petrology constraints and found that they systematically overestimate peak metamorphic temperatures. This discrepancy arises from a significant increase in Ti solubility at low pressures $$(<1$$ kbar). In fact, we demonstrate that a pressure difference of $$\sim 0.25$$ kbar within the aureole leads to an increase of 0.1 a.p.f.u. in Ti content, suggesting that pressure plays a key role in Ti incorporation at these low pressures. At lower pressures, the Ti-oxy substitution becomes saturated, and Ti incorporation is dominated by a Ti-spinel exchange mechanism. Additionally, textural and chemical analyses reveal that composition vary between small domains of a few hundred micrometers, indicating that local compositional heterogeneities significantly influences Ti content in biotite, even when a Ti-oxide and an Al-rich silicate are nearby. Finally, biotite starts growing near to the biotite-in isograd, and keeps on growing, so that its composition does not fully adjust to the peak composition due to the short metamorphic event. These findings highlight that both pressure and temperature influence the Ti content in biotite. The application of Ti-in-biotite thermometry requires careful consideration of equilibrium domains and growth kinetics.

Heat stress relief by tidally driven cold‐water bores on a coral reef atoll - Kelly Boden‐Hawes; Nicole L. Jones; Matthew D. Rayson; James P. Gilmour; Taryn Foster (Limnology and Oceanography, 2026)
Understanding how physical transport mechanisms influence coral reef temperature dynamics is crucial for effective management. Typically, sea surface temperature (SST) is used to estimate coral heat stress, yet subsurface physical processes can significantly influence reef temperature dynamics and are imperative to consider in predictive efforts. Using observations and a 3D numerical model, we conducted a volume‐based temperature budget analysis to investigate heat distribution at south Scott Reef, an atoll on the Australian North West Shelf. We identified how tidally driven processes influence the reef's heat budget by quantifying the volume flux of different temperature classes through each entrance. We found during the spring‐tide local, tidally driven cold‐water bores transported water ~ 2°C cooler than background through northwestern entrances of the lagoon semidiurnally leading to a net increase in cooler water. Coral surveys taken over the 2016 marine heatwave show sites exposed to the bores experienced a 0–10% reduction in coral cover compared to 10–60% in other regions. Using a dividing streamline model between January–May 1998–2022, we estimated water > 6°C cooler than recorded SST was delivered to the lagoon (40 m BSL) twice daily when tidally driven bores were active, that is, spring‐tide periods. Temperature differences between the surface and subsurface remained

eDNA2IQI: an eDNA/random forest-based prediction tool that accurately predicts ecological status for regulatory-compliance assessment - A.J. Wyness; T. Stoeck; B.J. Morrissey; I. Berrill; K. Davidson; C. FairBairn; S. MacIntyre; C. Webb; T. Foster; S. Brain; D. Svobodova; C. Clark; et al. (Aquaculture, 2026)

Estrogen-containing contraceptive use and blood lead concentrations in a cohort of premenopausal individuals - Lauren E. Chapman; Mandy S. Hall; Arianna Foster; Donna D. Baird; Quaker E. Harmon; Robert O. Wright; Julio A. Landero; Renee Heffron; Lauren A. Wise; Ganesa Wegienka; Ruth J. Geller; Amelia K. Wesselink; et al. (Environmental Research, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Parental Weaning Style Intent vs Reality: What Factors Affect If a Parent Intends and Completes Baby-led Weaning, Mixed Weaning, or Traditional Weaning - K. Whitley; D. Jacobvitz; S. Foster; L. Hernandez; M. Burgermaster; S. Dube; M. Abrego; A. Ramos-Gonzalez; M. Bradley; K. Ornelas; L. Sandoval-Mejia; I. Martinez; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

GDF-15 - Implications for Bladder Cancer Care and Symptom Control - B. Foster; R. Vargas; P. Srinivasan; D. Koestler; M. Bechtel; J. Holzbeierlein; M. Fisch; N. Henry; J. Unger; J. Hamilton-Reeves (Journal of the Academy of Nutrition and Dietetics, 2025)

Dietetics and Nursing Students Affirmatively Report the Likelihood of Recommending Predominantly Plant-based Diets for Non-communicable Disease Management - P. Dyett; L. Foster-Nicholas; C. Mitchell; V. Jones-Oyefeso; V. Sealey-Tobias; A. Adams-Robinson; P. Valley-Thom; D. Balfour (Journal of the Academy of Nutrition and Dietetics, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Speech Treatment for People with Cerebellar Multiple System Atrophy (MSA-C): A Pilot Randomised Controlled Trial of Two Approaches - Anja Lowit; Kaiyue Xing; D. Priya Shanmugarajah; Emma Foster; Suzanna Duty; David Young; Jan Stanier; Christopher Kobylecki; Marios Hadjivassiliou (The Cerebellum, 2025)
Speech problems are an early feature of Multiple System Atrophy (MSA). They can lead to social withdrawal and have significant impact on people’s quality of life. There is a considerable lack of clinical trials and clinicians lack guidance on how best to support this population. This project aimed to establish the feasibility and acceptability of a novel treatment approach, ClearSpeechTogether, in patients with the cerebellar variant of MSA (MSA-C), and to pilot an RCT comparing this treatment to standard speech and language therapy (SLT) treatment (ST). We recruited 24 patients with clinically probable MSA-C and dysarthria who were randomised to either treatment arm. Full data were available for 9 participants for ST, and 11 for ClearSpeechTogether. Both interventions lasted 6 weeks, ST offered 1 h of individual therapy a week, ClearSpeechTogether provided four individual therapy sessions over two weeks, followed by four weeks of daily, patient led group practice. Assessment and intervention were provided online via videoconferencing software. Data collection focused on feasibility, acceptability and signal of efficacy. Recruitment, conversion and attrition rates were within or close to target, and neither participants nor clinicians highlighted any acceptability issues. Communication outcomes were mixed, with biggest gains made in communication confidence and participation across both groups. Rapid decline in overall health status appeared to have impacted results. Results were generally positive and support the implementation of larger follow up trials. The study also demonstrated that people with MSA-C can benefit from speech therapy even at more severe stages of their disease progression.

Hypothermia treatment for ocular ischemia: A multiphase porous thermal model of human eye - D. Gongal; J.R. Hetling; C.D. Foster (Journal of Thermal Biology, 2025)

Association mapping of haploid male fertility in sweet corn - Tyler L. Foster; Ursula K. Frei; Mercy Fakude; Matheus D. Krause; Sarah Pfeffer; Somak Dutta; William F. Tracy; Marcio F. R. Resende; Thomas Lübberstedt (Theoretical and Applied Genetics, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

When can we detect lianas from space? Toward a mechanistic understanding of liana‐infested forest optics - Marco D. Visser; Matteo Detto; Félicien Meunier; Jin Wu; Jane R. Foster; David C. Marvin; Peter M. van Bodegom; Boris Bongalov; Matheus Henrique Nunes; David Coomes; Hans Verbeeck; J. Antonio Guzmán Q; et al. (Ecology, 2025)
Lianas, woody vines acting as structural parasites of trees, have profound effects on the composition and structure of tropical forests, impacting tree growth, mortality, and forest succession. Remote sensing could offer a powerful tool for quantifying the scale of liana infestation, provided the availability of robust detection methods. We analyze the consistency and global geographic specificity of spectral signals—reflectance across wavelengths—from liana‐infested tree crowns and forest stands, examining the underlying mechanisms of these signals. We compiled a uniquely comprehensive database, including leaf reflectance spectra from 5424 leaves, fine‐scale airborne reflectance data from 999 liana‐infested canopies, and coarse‐scale satellite reflectance data covering 775 ha of liana‐infested forest stands. To unravel the mechanisms of the liana spectral signal, we applied mechanistic radiative transfer models across scales, establishing a synthesis of the relative importance of different mechanisms, which we corroborate with field data on liana leaf chemistry and canopy structure. We find a consistent liana spectral signal at canopy and stand scales across globally distributed sites. This signature mainly arises at the canopy level due to direct effects of more horizontal leaf angles, resulting in a larger projected leaf area, and indirect effects from increased light scattering in the near and short‐wave infrared regions, linked to lianas' less costly leaf construction compared with trees on average. The existence of a consistent global spectral signal for lianas suggests that large‐scale quantification of liana infestation is feasible. However, because the traits responsible for the liana canopy‐reflectance signal are not exclusive to lianas, accurate large‐scale detection requires rigorously validated remote sensing methods. Our models highlight challenges in automated detection, such as potential misidentification due to leaf phenology, tree life history, topography, and climate, especially where the scale of liana infestation is less than a single remote sensing pixel. The observed cross‐site patterns also prompt ecological questions about lianas' adaptive similarities in optical traits across environments, indicating possible convergent evolution due to shared constraints on leaf biochemical and structural traits.

Identifying Priority Science Information Needs for Managing Public Lands - Sarah K. Carter; Travis S. Haby; Ella M. Samuel; Alison C. Foster; Jennifer K. Meineke; Laine E. McCall; Malia K. Burton; Christopher T. Domschke; Leigh D. Espy; Megan A. Gilbert (Environmental Management, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

2D geochemical imaging of biogenic marine carbonates using LA-TOF-ICP-MS at 1 and 2 μm pixel resolution - Christopher D. Standish; J. Andy Milton; Tessa M. Page; Rachel M. Brown; David Douglas; Bence Paul; Lukas Schlatt; Gavin L. Foster (Chemical Geology, 2024)

Historic ocean acidification of Loch Sween revealed by correlative geochemical imaging and high-resolution boron isotope analysis of Boreolithothamniom cf. soriferum - Ellen MacDonald; Gavin L. Foster; Christopher D. Standish; Jacob Trend; Tessa M. Page; Nicholas A. Kamenos (Earth and Planetary Science Letters, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

To improve estimates of neotropical forest carbon stocks more direct measurements are needed: An example from the Southwestern Amazon - Antonio Willian Flores de Melo; Adriano José Nogueira Lima; Marcus Vinicio Neves d’Oliveira; Joaquim dos Santos; I. Foster Brown; Eufran Ferreira do Amaral; Sonaira Souza da Silva; Igor Oliveira; Plínio Barbosa de Camargo; Niro Higuchi (Forest Ecology and Management, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Tectonic evolution of Macquarie Island: Oceanic crust, metamorphism, new-type of core complex and transpression - Ben D. Goscombe; David A. Foster; Ben Wade; Joshua J. Schwartz; Charles R. Jeffcoat (Gondwana Research, 2024)

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

International renal interest society best practice consensus guidelines for intermittent hemodialysis in dogs and cats - Gilad Segev; Jonathan D. Foster; Thierry Francey; Catherine Langston; Ariane Schweighauser; Larry D. Cowgill (The Veterinary Journal, 2024)

International Renal Interest Society best practice consensus guidelines for the diagnosis and management of acute kidney injury in cats and dogs - Gilad Segev; Stefano Cortellini; Jonathan D. Foster; Thierry Francey; Catherine Langston; Leonel Londoño; Ariane Schweighauser; Rosanne E. Jepson (The Veterinary Journal, 2024)

Geochemical proxies for deep-sea temperature and nutrient content in cold-water bamboo corals - Thomas J. Williams; Christopher D. Standish; Philippe Archambault; Jasmin A. Godbold; Martin Solan; Orestis L. Katsamenis; Philip J. Basford; Gavin L. Foster (Chemical Geology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Constraining uncertainty in boron isotope systematics using a Bayesian inversion engine reveals contrasting parameter sensitivities - Aled D. Evans; Gavin L. Foster; Damon A.H. Teagle (Chemical Geology, 2024)

Variable effects of substrate colour and microtexture on sessile marine taxa in Australian estuaries - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Craig D. H. Sherman; Cian Foster-Thorpe; Maria L. Vozzo; Katherine A. Dafforn (Biofouling, 2024)

A model to assess the environmental and economic impacts of municipal waste management in Europe - P.F. Albizzati; G. Foster; P. Gaudillat; S. Manfredi; D. Tonini (Waste Management, 2024)

Sorption and diffusion of per-polyfluoroalkyl substances (PFAS) in high-density polyethylene geomembranes - Aamir Ahmad; Kuo Tian; Burak Tanyu; Gregory D. Foster (Waste Management, 2024)

Environmental and socio-economic effects of construction and demolition waste recycling in the European Union - D. Caro; C. Lodato; A. Damgaard; J. Cristóbal; G. Foster; F. Flachenecker; D. Tonini (Science of The Total Environment, 2024)

A Comparison of Infant Diet Quality Indices in Infants 7-12 Months Old - S. Foster; D. Jacobvitz; L. Hernandez; H. Jones; M. Abrego; E. Widen (Journal of the Academy of Nutrition and Dietetics, 2023)

P25-14: Hepatic safety assessment of covalent inhibitor drug candidates - S. Amberntsson; B. Chouhan; A. Foster; G. Smith; S. Wilkinson; S. Harlfinger; S. Kavanagh; D. Williams (Toxicology Letters, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

A scenario-specific nexus modelling toolkit to identify trade-offs in the promotion of sustainable irrigated agriculture in Ecuador, a Belt and Road country - L. Naranjo; M.E. Correa-Cano; D. Rey; R. Chengot; F. España; M. Sactic; J.W. Knox; X. Yan; O. Viteri-Salazar; W. Foster; O. Melo (Journal of Cleaner Production, 2023)

Correction: Impact of nitrogen (N) and phosphorus (P) enrichment and skewed N:P stoichiometry on the skeletal formation and microstructure of symbiotic reef corals - M. C. Buckingham; C. D’Angelo; T. B. Chalk; G. L. Foster; K. G. Johnson; Z. Connelly; C. Olla; M. Saeed; J. Wiedenmann (Coral Reefs, 2023)

Geochemical responses of scleractinian corals to nutrient stress - C.D. Standish; T.B. Chalk; M. Saeed; F. Lei; M.C. Buckingham; C. D'Angelo; J. Wiedenmann; G.L. Foster (Geochimica et Cosmochimica Acta, 2023)

Variant-specific SARS-CoV-2 shedding rates in wastewater - Sarah M. Prasek; Ian L. Pepper; Gabriel K. Innes; Stephanie Slinski; Walter Q. Betancourt; Aidan R. Foster; Hayley D. Yaglom; W. Tanner Porter; David M. Engelthaler; Bradley W. Schmitz (Science of The Total Environment, 2023)

Boron isotopes in blue diamond record seawater-derived fluids in the lower mantle - Margo E. Regier; Karen V. Smit; Thomas B. Chalk; Thomas Stachel; Richard A. Stern; Evan M. Smith; Gavin L. Foster; Yannick Bussweiler; Chris DeBuhr; Antony D. Burnham; Jeff W. Harris; D. Graham Pearson (Earth and Planetary Science Letters, 2023)

Quantifying the impact of heat on human physical work capacity; part IV: interactions between work duration and heat stress severity - James W. Smallcombe; Josh Foster; Simon G. Hodder; Ollie Jay; Andreas D. Flouris; George Havenith (International Journal of Biometeorology, 2022)
High workplace temperatures negatively impact physical work capacity (PWC). Although PWC loss models with heat based on 1-h exposures are available, it is unclear if further adjustments are required to accommodate repeated work/rest cycles over the course of a full work shift. Therefore, we examined the impact of heat stress exposure on human PWC during a simulated work shift consisting of six 1-h work-rest cycles. Nine healthy males completed six 50-min work bouts, separated by 10-min rest intervals and an extended lunch break, on four separate occasions: once in a cool environment (15 °C/50% RH) and in three different air temperature and relative humidity combinations (moderate, 35 °C/50% RH; hot, 40 °C/50% RH; and very hot, 40 °C/70%). To mimic moderate to heavy workload, work was performed on a treadmill at a fixed heart rate of 130 beats·min −1 . During each work bout, PWC was quantified as the kilojoules expended above resting levels. Over the shift, work output per cycle decreased, even in the cool climate, with the biggest decrement after the lunch break and meal consumption. Expressing PWC relative to that achieved in the cool environment for the same work duration, there was an additional 5(± 4)%, 7(± 6)%, and 16(± 7)% decrease in PWC when work was performed across a full work shift for the moderate, hot, and very hot condition respectively, compared with 1-h projections. Empirical models to predict PWC based on the level of heat stress (Wet-Bulb Globe Temperature, Universal Thermal Climate Index, Psychrometric Wet-Bulb Temperature, Humidex, and Heat Index) and the number of work cycles performed are presented.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Impact of nitrogen (N) and phosphorus (P) enrichment and skewed N:P stoichiometry on the skeletal formation and microstructure of symbiotic reef corals - M. C. Buckingham; C. D’Angelo; T. B. Chalk; G. L. Foster; K. G. Johnson; Z. Connelly; C. Olla; M. Saeed; J. Wiedenmann (Coral Reefs, 2022)
Reported divergent responses of coral growth and skeletal microstructure to the nutrient environment complicate knowledge-based management of water quality in coral reefs. By re-evaluating published results considering the taxonomy of the studied corals and the N:P stoichiometry of their nutrient environment, we could resolve some of the major apparent contradictions. Our analysis suggests that Acroporids behave differently to several other common genera and show distinct responses to specific nutrient treatments. We hypothesised that both the concentrations of dissolved inorganic N and P in the water and their stoichiometry shape skeletal growth and microstructure. We tested this hypothesis by exposing Acropora polystoma fragments to four nutrient treatments for > 10 weeks: high nitrate/high phosphate (HNHP), high nitrate/low phosphate (HNLP), low nitrate/high phosphate (LNHP) and low nitrate/low phosphate (LNLP). HNHP corals retained high zooxanthellae densities and their linear extension and calcification rates were up to ten times higher than in the other treatments. HNLP and LNLP corals bleached through loss of symbionts. The photochemical efficiency (Fv/Fm) of residual symbionts in HNLP corals was significantly reduced, indicating P-starvation. Micro-computed tomography (µCT) of the skeletal microstructure revealed that reduced linear extension in nutrient limited or nutrient starved conditions (HNLP, LNHP, LNLP) was associated with significant thickening of skeletal elements and reduced porosity. These changes can be explained by the strongly reduced linear extension rate in combination with a smaller reduction in the calcification rate. Studies using increased skeletal density as a proxy for past thermal bleaching events should consider that such an increase in density may also be associated with temperature-independent response to the nutrient environment. Furthermore, the taxonomy of corals and seawater N:P stoichiometry should be considered when analysing and managing the impacts of nutrient pollution.

Cold‐air pools as microrefugia for ecosystem functions in the face of climate change - Melissa A. Pastore; Aimée T. Classen; Anthony W. D'Amato; Jane R. Foster; E. Carol Adair (Ecology, 2022)
Cold‐air pooling is a global phenomenon that frequently sustains low temperatures in sheltered, low‐lying depressions and valleys and drives other key environmental conditions, such as soil temperature, soil moisture, vapor pressure deficit, frost frequency, and winter dynamics. Local climate patterns in areas prone to cold‐air pooling are partly decoupled from regional climates and thus may be buffered from macroscale climate change. There is compelling evidence from studies across the globe that cold‐air pooling impacts plant communities and species distributions, making these decoupled microclimate areas potentially important microrefugia for species under climate warming. Despite interest in the potential for cold‐air pools to enable species persistence under warming, studies investigating the effects of cold‐air pooling on ecosystem processes are scarce. Because local temperatures and vegetation composition are critical drivers of ecosystem processes like carbon cycling and storage, cold‐air pooling may also act to preserve ecosystem functions. We review research exploring the ecological impacts of cold‐air pooling with a focus on vegetation, and then present a new conceptual framework in which cold‐air pooling creates feedbacks between species and ecosystem properties that generate unique hotspots for carbon accrual in some systems relative to areas more vulnerable to regional climate change impacts. Finally, we describe key steps to motivate future research investigating the potential for cold‐air pools to serve as microrefugia for ecosystem functions under climate change.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Microbial mediators of plant community response to long‐term N and P fertilization: Evidence of a role of plant responsiveness to mycorrhizal fungi - Guangzhou Wang; Liz Koziol; Bryan L. Foster; James D. Bever (Global Change Biology, 2022)
Climate changes and anthropogenic nutrient enrichment widely threaten plant diversity and ecosystem functions. Understanding the mechanisms governing plant species turnover across nutrient gradients is crucial to developing successful management and restoration strategies. We tested whether and how soil microbes, particularly arbuscular mycorrhizal fungi (AMF), could mediate plant community response to a 15 years long‐term N (0, 4, 8, and 16 g N m −2 year −1 ) and P (0 and 8 g N m −2 year −1 ) enrichment in a grassland system. We found N and P enrichment resulted in plant community diversity decrease and composition change, in which perennial C 4 graminoids were dramatically reduced while annuals and perennial forbs increased. Metabarcoding analysis of soil fungal community showed that N and P changed fungal diversity and composition, of which only a cluster of AMF identified by the co‐occurrence networks analysis was highly sensitive to P treatments and was negatively correlated with shifts in percentage cover of perennial C 4 graminoids. Moreover, by estimating the mycorrhizal responsiveness (MR) of 41 plant species in the field experiment from 264 independent tests, we found that the community weighted mean MR of the plant community was substantially reduced with nutrient enrichment and was positively correlated with C 4 graminoids percentage cover. Both analyses of covariance and structural equation modeling indicated that the shift in MR rather than AMF composition change was the primary predictor of the decline in perennial C 4 graminoids, suggesting that the energy cost invested by C 4 plants on those sensitive AMF might drive the inferior competitive abilities compared with other groups. Our results suggest that shifts in the competitive ability of mycorrhizal responsive plants can drive plant community change to anthropogenic eutrophication, suggesting a functional benefit of mycorrhizal mutualism in ecological restoration following climatic or anthropogenic degradation of soil communities.

Quantifying the impact of heat on human physical work capacity; part II: the observed interaction of air velocity with temperature, humidity, sweat rate, and clothing is not captured by most heat stress indices - Josh Foster; James W. Smallcombe; Simon Hodder; Ollie Jay; Andreas D. Flouris; George Havenith (International Journal of Biometeorology, 2022)
Increasing air movement can alleviate or exacerbate occupational heat strain, but the impact is not well defined across a wide range of hot environments, with different clothing levels. Therefore, we combined a large empirical study with a physical model of human heat transfer to determine the climates where increased air movement (with electric fans) provides effective body cooling. The model allowed us to generate practical advice using a high-resolution matrix of temperature and humidity. The empirical study involved a total of 300 1-h work trials in a variety of environments (35, 40, 45, and 50 °C, with 20 up to 80% relative humidity) with and without simulated wind (3.5 vs 0.2 m∙s −1 ), and wearing either minimal clothing or a full body work coverall. Our data provides compelling evidence that the impact of fans is strongly determined by air temperature and humidity. When air temperature is ≥ 35 °C, fans are ineffective and potentially harmful when relative humidity is below 50%. Our simulated data also show the climates where high wind/fans are beneficial or harmful, considering heat acclimation, age, and wind speed. Using unified weather indices, the impact of air movement is well captured by the universal thermal climate index, but not by wet-bulb globe temperature and aspirated wet-bulb temperature. Overall, the data from this study can inform new guidance for major public and occupational health agencies, potentially maintaining health and productivity in a warming climate.

Quantifying the impact of heat on human physical work capacity; part III: the impact of solar radiation varies with air temperature, humidity, and clothing coverage - Josh Foster; James W. Smallcombe; Simon Hodder; Ollie Jay; Andreas D. Flouris; Lars Nybo; George Havenith (International Journal of Biometeorology, 2022)
Heat stress decreases human physical work capacity (PWC), but the extent to which solar radiation (SOLAR) compounds this response is not well understood. This study empirically quantified how SOLAR impacts PWC in the heat, considering wide, but controlled, variations in air temperature, humidity, and clothing coverage. We also provide correction equations so PWC can be quantified outdoors using heat stress indices that do not ordinarily account for SOLAR (including the Heat Stress Index, Humidex, and Wet-Bulb Temperature). Fourteen young adult males (7 donning a work coverall, 7 with shorts and trainers) walked for 1 h at a fixed heart rate of 130 beats∙min − 1, in seven combinations of air temperature (25 to 45°C) and relative humidity (20 or 80%), with and without SOLAR (800 W/m 2 from solar lamps). Cumulative energy expenditure in the heat, relative to the work achieved in a cool reference condition, was used to determine PWC%. Skin temperature was the primary determinant of PWC in the heat. In dry climates with exposed skin (0.3 Clo), SOLAR caused PWC to decrease exponentially with rising air temperature, whereas work coveralls (0.9 Clo) negated this effect. In humid conditions, the SOLAR-induced reduction in PWC was consistent and linear across all levels of air temperature and clothing conditions. Wet-Bulb Globe Temperature and the Universal Thermal Climate Index represented SOLAR correctly and did not require a correction factor. For the Heat Stress Index, Humidex, and Wet-Bulb Temperature, correction factors are provided enabling forecasting of heat effects on work productivity.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Future changes in the distribution of two non-indigenous orchids and their acquired enemy in Puerto Rico - Evan A. Foster; James D. Ackerman (Biological Invasions, 2021)

Regional Variation in Winter Foraging Strategies by Weddell Seals in Eastern Antarctica and the Ross Sea - Rob Harcourt; Mark A. Hindell; Clive R. McMahon; Kimberly T. Goetz; Jean-Benoit Charrassin; Karine Heerah; Rachel Holser; Ian D. Jonsen; Michelle R. Shero; Xavier Hoenner; Rose Foster; Baukje Lenting; et al. (Frontiers in Marine Science, 2021)
The relative importance of intrinsic and extrinsic determinants of animal foraging is often difficult to quantify. The most southerly breeding mammal, the Weddell seal, remains in the Antarctic pack-ice year-round. We compared Weddell seals tagged at three geographically and hydrographically distinct locations in East Antarctica (Prydz Bay, Terre Adélie , and the Ross Sea) to quantify the role of individual variability and habitat structure in winter foraging behaviour. Most Weddell seals remained in relatively small areas close to the coast throughout the winter, but some dispersed widely. Individual utilisation distributions ( UDi , a measure of the total area used by an individual seal) ranged from 125 to 20,825 km 2 . This variability was not due to size or sex but may be due to other intrinsic states for example reproductive condition or personality. The type of foraging (benthic vs. pelagic) varied from 56.6 ± 14.9% benthic dives in Prydz Bay through 42.1 ± 9.4% Terre Adélie to only 25.1 ± 8.7% in the Ross Sea reflecting regional hydrographic structure. The probability of benthic diving was less likely the deeper the ocean. Ocean topography was also influential at the population level; seals from Terre Adélie , with its relatively narrow continental shelf, had a core (50%) UD of only 200 km 2 , considerably smaller than the Ross Sea (1650 km 2 ) and Prydz Bay (1700 km 2 ). Sea ice concentration had little influence on the time the seals spent in shallow coastal waters, but in deeper offshore water they used areas of higher ice concentration. Marine Protected Areas (MPAs) in the Ross Sea encompass all the observed Weddell seal habitat, and future MPAs that include the Antarctic continental shelf are likely to effectively protect key Weddell seal habitat.

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

An advanced empirical model for quantifying the impact of heat and climate change on human physical work capacity - Josh Foster; James W. Smallcombe; Simon Hodder; Ollie Jay; Andreas D. Flouris; Lars Nybo; George Havenith (International Journal of Biometeorology, 2021)
Occupational heat stress directly hampers physical work capacity (PWC), with large economic consequences for industries and regions vulnerable to global warming. Accurately quantifying PWC is essential for forecasting impacts of different climate change scenarios, but the current state of knowledge is limited, leading to potential underestimations in mild heat, and overestimations in extreme heat. We therefore developed advanced empirical equations for PWC based on 338 work sessions in climatic chambers (low air movement, no solar radiation) spanning mild to extreme heat stress. Equations for PWC are available based on air temperature and humidity, for a suite of heat stress assessment metrics, and mean skin temperature. Our models are highly sensitive to mild heat and to our knowledge are the first to include empirical data across the full range of warm and hot environments possible with future climate change across the world. Using wet bulb globe temperature (WBGT) as an example, we noted 10% reductions in PWC at mild heat stress (WBGT = 18°C) and reductions of 78% in the most extreme conditions (WBGT = 40°C). Of the different heat stress indices available, the heat index was the best predictor of group level PWC ( R 2 = 0.96) but can only be applied in shaded conditions. The skin temperature, but not internal/core temperature, was a strong predictor of PWC ( R 2 = 0.88), thermal sensation ( R 2 = 0.84), and thermal comfort ( R 2 = 0.73). The models presented apply to occupational workloads and can be used in climate projection models to predict economic and social consequences of climate change.

Watershed characteristics influence winter stream temperature in a forested landscape - Warren D. Devine; E. Ashley Steel; Alex D. Foster; Teodora V. Minkova; Kyle D. Martens (Aquatic Sciences, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Genetic analyses of native Fusarium head blight resistance in two spring wheat populations identifies QTL near the B1, Ppd-D1, Rht-1, Vrn-1, Fhb1, Fhb2, and Fhb5 loci - Dinushika Thambugala; Anita L. Brûlé-Babel; Barbara A. Blackwell; George Fedak; Adam J. Foster; Dan MacEachern; Jeannie Gilbert; Maria Antonia Henriquez; Richard A. Martin; Brent D. McCallum; Dean Spaner; Muhammad Iqbal; et al. (Theoretical and Applied Genetics, 2020)

Contribution of NDM and OXA-type carbapenemases to carbapenem resistance in clinical Acinetobacter baumannii from Nigeria - David O. Ogbolu; Oyebode A. Terry Alli; Adeolu S. Oluremi; Y. Temilola Ogunjimi; D. Iyanu Ojebode; Veronica Dada; Olubunmi O. Alaka; Ebenezer Foster-Nyarko; Mark A. Webber (Infectious Diseases, 2020)

Direct administration of ifenprodil and citalopram into the nucleus accumbens inhibits cue-induced nicotine seeking and associated glutamatergic plasticity - Jonna M. Leyrer-Jackson; Jose A. Piña; Joseph McCallum; M. Foster Olive; Cassandra D. Gipson (Brain Structure and Function, 2020)

Mode of miniaturisation influences body shape evolution in New World anchovies (Engraulidae) - Devin D. Bloom; Matthew Kolmann; Kimberly Foster; Helen Watrous (Journal of Fish Biology, 2020)
We explored the macroevolutionary dynamics of miniaturisation in New World anchovies by integrating a time‐calibrated phylogeny, geometric morphometrics and phylogenetic comparative methods. We found that the paedomorphic species Amazonsprattus scintilla occupies a novel region of shape space, while the dwarf species Anchoviella manamensis has an overall shape consistent with other anchovies. We found that miniaturisation did not increase overall clade disparity in size or shape beyond the expectations of Brownian motion, nor were there differences in rates of size or shape evolution among clades. Overall, our study shows that while the mode of miniaturisation influences shape evolution, the phenotypic novelty produced by the evolution of miniaturisation did not seem to alter macroevolutionary dynamics.

Utilization of infectious clones to visualize Cassava brown streak virus replication in planta and gain insights into symptom development - Katie R. Tomlinson; Susan E. Seal; Andy M. Bailey; Gary D. Foster (Virus Genes, 2019)

Designing Monitoring Programs for Marine Protected Areas Within an Evidence Based Decision Making Paradigm - Keith R. Hayes; Geoffrey R. Hosack; Emma Lawrence; Paul Hedge; Neville S. Barrett; Rachel Przeslawski; M. Julian Caley; Scott D. Foster (Frontiers in Marine Science, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Stream Conditions after 18 Years of Passive Riparian Restoration in Small Fish-bearing Watersheds - Kyle D. Martens; Warren D. Devine; Teodora V. Minkova; Alex D. Foster (Environmental Management, 2019)

Sedimentary profiles of pollution marker chemicals along a large tributary of Chesapeake Bay (mid-Atlantic USA) - Gregory D. Foster; Cassi Walls; Phillip R. McEachern; Thomas B. Huff; Randolph McBride (Journal of Soils and Sediments, 2019)

Corrigendum: Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2019)

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

Ambient changes exceed treatment effects on plant species abundance in global change experiments - J. Adam Langley; Samantha K. Chapman; Kimberly J. La Pierre; Meghan Avolio; William D. Bowman; David S. Johnson; Forest Isbell; Kevin R. Wilcox; Bryan L. Foster; Mark J. Hovenden; Alan K. Knapp; Sally E. Koerner; et al. (Global Change Biology, 2018)
The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO 2 , nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2,116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes.

Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2018)
Aim We analysed a dataset composed of multiple palaeoclimate and lake‐sediment pollen records from New England to explore how postglacial changes in the composition and spatial patterns of vegetation were controlled by regional‐scale climate change, a subregional environmental gradient, and landscape‐scale variations in soil characteristics. Location The 120,000‐km 2 study area includes parts of Vermont and New Hampshire in the north, where sites are 150–200 km from the Atlantic Ocean, and spans the coastline from southeastern New York to Cape Cod and the adjacent islands, including Block Island, the Elizabeth Islands, Nantucket, and Martha's Vineyard. Methods We analysed pollen records from 29 study sites, using multivariate cluster analysis to visualize changes in the composition and spatial patterns of vegetation during the last 14,000 years. The pollen data were compared with temperature and precipitation reconstructions. Results Boreal forest featuring Picea and Pinus banksiana was present across the region when conditions were cool and dry 14,000–12,000 calibrated 14 C years before present (ybp). Pinus strobus became regionally dominant as temperatures increased between 12,000 and 10,000 ybp. The composition of forests in inland and coastal areas diverged in response to further warming after 10,000 ybp, when Quercus and Pinus rigida expanded across southern New England, whereas conditions remained cool enough in inland areas to maintain Pinus strobus . Increasing precipitation allowed Tsuga canadensis , Fagus grandifolia , and Betula to replace Pinus strobus in inland areas during 9,000–8,000 ybp, and also led to the expansion of Carya across the coastal part of the region beginning at 7,000–6,000 ybp. Abrupt cooling at 5,500–5,000 ybp caused sharp declines in Tsuga in inland areas and Quercus at some coastal sites, and the populations of those taxa remained low until they recovered around 3,000 ybp in response to rising precipitation. Throughout most of the Holocene, sites underlain by sandy glacial deposits were occupied by Pinus rigida and Quercus . Main conclusions Postglacial changes in the composition and spatial pattern of New England forests were controlled by long‐term trends and abrupt shifts in temperature and precipitation, as well as by the environmental gradient between coastal and inland parts of the region. Substrate and soil moisture shaped landscape‐scale variations in forest composition.

Environmental engagement in troubled times: a manifesto - James D. Proctor; Jennifer Bernstein; Philip Brick; Emma Brush; Susan Caplow; Kenneth Foster (Journal of Environmental Studies and Sciences, 2018)

An analysis of potential controls on long-term 137Cs accumulation in the sediments of UK lakes - Simon Pulley; Ian D. L. Foster; Adrian L. Collins; Yusheng Zhang; Jennine Evans (Journal of Paleolimnology, 2018)

The duality of ocean acidification as a resource and a stressor - Sean D. Connell; Zoë A. Doubleday; Nicole R. Foster; Sarah B. Hamlyn; Christopher D. G. Harley; Brian Helmuth; Brendan P. Kelaher; Ivan Nagelkerken; Kirsten L. Rodgers; Gianluca Sarà; Bayden D. Russell (Ecology, 2018)
Ecologically dominant species often define ecosystem states, but as human disturbances intensify, their subordinate counterparts increasingly displace them. We consider the duality of disturbance by examining how environmental drivers can simultaneously act as a stressor to dominant species and as a resource to subordinates. Using a model ecosystem, we demonstrate that CO 2 ‐driven interactions between species can account for such reversals in dominance; i.e., the displacement of dominants (kelp forests) by subordinates (turf algae). We established that CO 2 enrichment had a direct positive effect on productivity of turfs, but a negligible effect on kelp. CO 2 enrichment further suppressed the abundance and feeding rate of the primary grazer of turfs (sea urchins), but had an opposite effect on the minor grazer (gastropods). Thus, boosted production of subordinate producers, exacerbated by a net reduction in its consumption by primary grazers, accounts for community change (i.e., turf displacing kelp). Ecosystem collapse, therefore, is more likely when resource enrichment alters competitive dominance of producers, and consumers fail to compensate. By recognizing such duality in the responses of interacting species to disturbance, which may stabilize or exacerbate change, we can begin to understand how intensifying human disturbances determine whether or not ecosystems undergo phase shifts.

Loss of the nutrient sensor TAS1R3 leads to reduced bone resorption - Michael S. Eaton; Nicholas Weinstein; Jordan B. Newby; Maggie M. Plattes; Hanna E. Foster; Jon W. Arthur; Taylor D. Ward; Stephen R. Shively; Ryann Shor; Justin Nathan; Hannah M. Davis; Lilian I. Plotkin; et al. (Journal of Physiology and Biochemistry, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Simultaneous vegetation classification and mapping at large spatial scales - Mitchell B. Lyons; Scott D. Foster; David A. Keith (Journal of Biogeography, 2017)
Aim Multivariate mixture models offer the ability to streamline the typically multi‐stage process of vegetation classification and mapping into a single, simultaneous analytical step. Our aim is to demonstrate the model's utility over large and diverse areas, with comparison to existing classification and mapping conventions. Location New South Wales, Australia. Methods We demonstrate a statistical model that uses both multivariate species data and environmental covariate data to simultaneously classify observations into groups and predict those groups out into environmental and geographical space. We used two large data sets to demonstrate the method: an ~810,000 km 2 area with 4,715 sites and 488 species and a ~220,000 km 2 area with 5,183 sites and 446 species. A range of topographic, terrain, climate and soil predictors were used as environmental variables, including future projected climate variables. Models can be fit with the R package “ RCP mod.” Results The method results in probabilistic memberships to vegetation assemblages, for both the classification and map. There was general agreement between our approach and existing vegetation classification conventions, but we explore some notable differences. We were able to examine the environmental gradients that define the predicted vegetation distributions, as well as make predictions about how the distribution of species assemblages might shift as a result of climate change. Main conclusions Our approach tightens the link between description of biodiversity patterns and their depiction in space, by considering both biotic and spatially explicit abiotic information simultaneously. The method allows uncertainty to be quantified objectively across a consistent set of groups for both vegetation classification and mapping, which is rarely the case in traditional multi‐stage approaches. A simultaneous modelling approach increases capacity to make predictions into varying spatial, temporal and environmental dimensions, providing new ecological insights and increasing capacity for evidence‐based decision making.

Hydrogeological typologies of the Indo-Gangetic basin alluvial aquifer, South Asia - H. C. Bonsor; A. M. MacDonald; K. M. Ahmed; W. G. Burgess; M. Basharat; R. C. Calow; A. Dixit; S. S. D. Foster; K. Gopal; D. J. Lapworth; M. Moench; A. Mukherjee; et al. (Hydrogeology Journal, 2017)

Infliximab Maintenance Dosing in Inflammatory Bowel Disease: an Example for In Silico Assessment of Adaptive Dosing Strategies - Jessica Wojciechowski; Richard N. Upton; Diane R. Mould; Michael D. Wiese; David J. R. Foster (The AAPS Journal, 2017)

Simulations of a Cold-Air Pool in Utah’s Salt Lake Valley: Sensitivity to Land Use and Snow Cover - Christopher S. Foster; Erik T. Crosman; John D. Horel (Boundary-Layer Meteorology, 2017)

Laboratory bioassays and field-cage trials of Metarhizium spp. isolates with field-collected Mormon crickets (Anabrus simplex) - Chad A. Keyser; Éverton K. K. Fernandes; Drauzio E. N. Rangel; R. Nelson Foster; Larry E. Jech; K. Chris Reuter; Lonnie R. Black; Stefan Jaronski; Darl D. Flake; Edward W. Evans; Donald W. Roberts (BioControl, 2017)

High Resolution Ultrasound Superharmonic Perfusion Imaging: In Vivo Feasibility and Quantification of Dynamic Contrast-Enhanced Acoustic Angiography - Brooks D. Lindsey; Sarah E. Shelton; K. Heath Martin; Kathryn A. Ozgun; Juan D. Rojas; F. Stuart Foster; Paul A. Dayton (Annals of Biomedical Engineering, 2017)

Historic grazing in southern New England, USA, recorded by fungal spores in lake sediments - Maria E. Orbay-Cerrato; W. Wyatt Oswald; Elaine D. Doughty; David R. Foster; Brian R. Hall (Vegetation History and Archaeobotany, 2017)

Long‐term structural and biomass dynamics of virgin Tsuga canadensis–Pinus strobus forests after hurricane disturbance - Anthony W. D'Amato; David A. Orwig; David R. Foster; Audrey Barker Plotkin; Peter K. Schoonmaker; Maggie R. Wagner (Ecology, 2017)
The development of old‐growth forests in northeastern North America has largely been within the context of gap‐scale disturbances given the rarity of stand‐replacing disturbances. Using the 10‐ha old‐growth Harvard Tract and its associated 90‐year history of measurements, including detailed surveys in 1989 and 2009, we document the long‐term structural and biomass development of an old‐growth Tsuga canadensis–Pinus strobus forest in southern New Hampshire, USA following a stand‐replacing hurricane in 1938. Measurements of aboveground biomass pools were integrated with data from second‐ and old‐growth T. canadensis forests to evaluate long‐term patterns in biomass development following this disturbance. Ecosystem structure across the Tract prior to the hurricane exhibited a high degree of spatial heterogeneity with the greatest levels of live tree basal area (70–129 m 2 /ha) on upper west‐facing slopes where P. strobus was dominant and intermixed with T. canadensis . Live‐tree biomass estimates for these stratified mixtures ranged from 159 to 503 Mg/ha at the localized, plot scale (100 m 2 ) and averaged 367 Mg/ha across these portions of the landscape approaching the upper bounds for eastern forests. Live‐tree biomass 71 years after the hurricane is more uniform and lower in magnitude, with T. canadensis currently the dominant overstory tree species throughout much of the landscape. Despite only one living P. strobus stem in the 2009 plots (and fewer than five stems known across the entire 10‐ha area), the detrital legacy of this species is pronounced with localized accumulations of coarse woody debris exceeding 237.7–404.2 m 3 /ha where this species once dominated the canopy. These patterns underscore the great sizes P. strobus attained in pre‐European landscapes and its great decay resistance relative to its forest associates. Total aboveground biomass pools in this 71‐year‐old forest (255 Mg/ha) are comparable to those in modern old‐growth ecosystems in the region that also lack abundant white pine. Results highlight the importance of disturbance legacies in affecting forest structural conditions over extended periods following stand‐replacing events and underscore that post‐disturbance salvage logging can alter ecosystem development for decades. Moreover, the dominant role of old‐growth P. strobus in live and detrital biomass pools before and after the hurricane, respectively, demonstrate the disproportionate influence this species likely had on carbon storage at localized scales prior to the widespread, selective harvesting of large P. strobus across the region in the 18th and 19th centuries.

Freeze–thaw cycles have minimal effect on the mineralisation of low molecular weight, dissolved organic carbon in Arctic soils - A. Foster; D. L. Jones; E. J. Cooper; P. Roberts (Polar Biology, 2016)

Comparative metabonomic analysis of hepatotoxicity induced by acetaminophen and its less toxic meta-isomer - Michael Kyriakides; Lea Maitre; Brendan D. Stamper; Isaac Mohar; Terrance J. Kavanagh; John Foster; Ian D. Wilson; Elaine Holmes; Sidney D. Nelson; Muireann Coen (Archives of Toxicology, 2016)

Functional analysis of Agaricus bisporus serine proteinase 1 reveals roles in utilization of humic rich substrates and adaptation to the leaf‐litter ecological niche - Mary N. Heneghan; Claire Burns; Ana M. S. B. Costa; Kerry S. Burton; Michael P. Challen; Andy M. Bailey; Gary D. Foster (Environmental Microbiology, 2016)
Summary Agaricus bisporus is a secondary decomposer fungus and an excellent model for the adaptation, persistence and growth of fungi in humic‐rich environments such as soils of temperate woodland and pastures. The A. bisporus serine proteinase SPR1 is induced by humic acids and is highly expressed during growth on compost. Three Spr1 gene silencing cassettes were constructed around sense, antisense and non‐translatable‐stop strategies (pGRsensehph, pGRantihph and pGRstophph). Transformation of A. bisporus with these cassettes generated cultures showing a reduction in extracellular proteinase activity as demonstrated by the reduction, or abolition, of a clearing zone on plate‐based bioassays. These lines were then assessed by detailed enzyme assay, RT‐qPCR and fruiting. Serine proteinase activity in liquid cultures was reduced in 83% of transformants. RT‐qPCR showed reduced Spr1 mRNA levels in all transformants analysed, and these correlated with reduced enzyme activity. When fruiting was induced, highly‐silenced transformant AS5 failed to colonize the compost, whilst for those that did colonize the compost, 60% gave a reduction in mushroom yield. Transcriptional, biochemical and developmental observations, demonstrate that SPR1 has an important role in nutrient acquisition in compost and that SPR1 is a key enzyme in the adaptation of Agaricus to the humic‐rich ecological niche formed during biomass degradation.

Imperfect observations in ecological studies - Hideyasu Shimadzu; Scott D. Foster; Ross Darnell (Environmental and Ecological Statistics, 2016)

Microbial dinitrogen fixation in coral holobionts exposed to thermal stress and bleaching - Ulisse Cardini; Nanne van Hoytema; Vanessa N. Bednarz; Laura Rix; Rachel A. Foster; Mamoon M. D. Al‐Rshaidat; Christian Wild (Environmental Microbiology, 2016)
Summary Coral holobionts (i.e., coral‐algal‐prokaryote symbioses) exhibit dissimilar thermal sensitivities that may determine which coral species will adapt to global warming. Nonetheless, studies simultaneously investigating the effects of warming on all holobiont members are lacking. Here we show that exposure to increased temperature affects key physiological traits of all members (herein: animal host, zooxanthellae and diazotrophs) of both Stylophora pistillata and Acropora hemprichii during and after thermal stress. S. pistillata experienced severe loss of zooxanthellae (i.e., bleaching) with no net photosynthesis at the end of the experiment. Conversely, A. hemprichii was more resilient to thermal stress. Exposure to increased temperature (+ 6°C) resulted in a drastic increase in daylight dinitrogen (N 2 ) fixation, particularly in A. hemprichii (threefold compared with controls). After the temperature was reduced again to in situ levels, diazotrophs exhibited a reversed diel pattern of activity, with increased N 2 fixation rates recorded only in the dark, particularly in bleached S. pistillata (twofold compared to controls). Concurrently, both animal hosts, but particularly bleached S. pistillata , reduced both organic matter release and heterotrophic feeding on picoplankton. Our findings indicate that physiological plasticity by coral‐associated diazotrophs may play an important role in determining the response of coral holobionts to ocean warming.

Inorganic Arsenic Concentrations in Wheat Chaff Exceed Those in Wheat Grain - Elliott G. Duncan; William A. Maher; Rajani Jagtap; Simon D. Foster; Frank Krikowa; Cathryn A. O’Sullivan; Margaret M. Roper (Water, Air, & Soil Pollution, 2016)

Predicting tree biomass growth in the temperate–boreal ecotone: Is tree size, age, competition, or climate response most important? - Jane R. Foster; Andrew O. Finley; Anthony W. D'Amato; John B. Bradford; Sudipto Banerjee (Global Change Biology, 2016)
As global temperatures rise, variation in annual climate is also changing, with unknown consequences for forest biomes. Growing forests have the ability to capture atmospheric CO 2 and thereby slow rising CO 2 concentrations. Forests’ ongoing ability to sequester C depends on how tree communities respond to changes in climate variation. Much of what we know about tree and forest response to climate variation comes from tree‐ring records. Yet typical tree‐ring datasets and models do not capture the diversity of climate responses that exist within and among trees and species. We address this issue using a model that estimates individual tree response to climate variables while accounting for variation in individuals’ size, age, competitive status, and spatially structured latent covariates. Our model allows for inference about variance within and among species. We quantify how variables influence aboveground biomass growth of individual trees from a representative sample of 15 northern or southern tree species growing in a transition zone between boreal and temperate biomes. Individual trees varied in their growth response to fluctuating mean annual temperature and summer moisture stress. The variation among individuals within a species was wider than mean differences among species. The effects of mean temperature and summer moisture stress interacted, such that warm years produced positive responses to summer moisture availability and cool years produced negative responses. As climate models project significant increases in annual temperatures, growth of species like Acer saccharum , Quercus rubra , and Picea glauca will vary more in response to summer moisture stress than in the past. The magnitude of biomass growth variation in response to annual climate was 92–95% smaller than responses to tree size and age. This means that measuring or predicting the physical structure of current and future forests could tell us more about future C dynamics than growth responses related to climate change alone.

Montane forest ecotones moved downslope in northeastern USA in spite of warming between 1984 and 2011 - Jane R. Foster; Anthony W. D'Amato (Global Change Biology, 2015)
Ecotones are transition zones that form, in forests, where distinct forest types meet across a climatic gradient. In mountains, ecotones are compressed and act as potential harbingers of species shifts that accompany climate change. As the climate warms in New England, USA , high‐elevation boreal forests are expected to recede upslope, with northern hardwood species moving up behind. Yet recent empirical studies present conflicting findings on this dynamic, reporting both rapid upward ecotonal shifts and concurrent increases in boreal species within the region. These discrepancies may result from the limited spatial extent of observations. We developed a method to model and map the montane forest ecotone using Landsat imagery to observe change at scales not possible for plot‐based studies, covering mountain peaks over 39 000 km 2 . Our results show that ecotones shifted downward or stayed stable on most mountains between 1991 and 2010, but also shifted upward in some cases (13–15% slopes). On average, upper ecotone boundaries moved down −1.5 m yr −1 in the Green Mountains, VT , and −1.3 m yr −1 in the White Mountains, NH . These changes agree with remeasured forest inventory data from Hubbard Brook Experimental Forest, NH , and suggest that processes of boreal forest recovery from prior red spruce decline, or human land use and disturbance, may swamp out any signal of climate‐mediated migration in this ecosystem. This approach represents a powerful framework for evaluating similar ecotonal dynamics in other mountainous regions of the globe.

Interactive effects of fire and large herbivores on web-building spiders - C. N. Foster; P. S. Barton; J. T. Wood; D. B. Lindenmayer (Oecologia, 2015)

Climate remains an important driver of post‐European vegetation change in the eastern United States - Neil Pederson; Anthony W. D'Amato; James M. Dyer; David R. Foster; David Goldblum; Justin L. Hart; Amy E. Hessl; Louis R. Iverson; Stephen T. Jackson; Dario Martin‐Benito; Brian C. McCarthy; Ryan W. McEwan; et al. (Global Change Biology, 2015)

Model-based thinking for community ecology - David I. Warton; Scott D. Foster; Glenn De’ath; Jakub Stoklosa; Piers K. Dunstan (Plant Ecology, 2015)

Dormancy and growth of metastatic breast cancer cells in a bone-like microenvironment - Donna M. Sosnoski; Robert J. Norgard; Cassidy D. Grove; Shelby J. Foster; Andrea M. Mastro (Clinical & Experimental Metastasis, 2015)

Ploidy Level Affects Important Biomass Traits of Novel Shrub Willow (Salix) Hybrids - Michelle J. Serapiglia; Fred E. Gouker; J. Foster Hart; Faride Unda; Shawn D. Mansfield; Arthur J. Stipanovic; Lawrence B. Smart (BioEnergy Research, 2015)

Total arsenic concentrations and arsenic species present in naturally decomposing Ecklonia radiata tissues collected from various marine habitats - Elliott G Duncan; William A Maher; Simon D Foster; Frank Krikowa (Journal of Applied Phycology, 2014)

The influence of bacteria on the arsenic species produced by laboratory cultures of the marine phytoplankton Dunaliella tertiolecta - Elliott G. Duncan; William A. Maher; Simon D. Foster; Katarina M. Mikac; Frank Krikowa (Journal of Applied Phycology, 2014)

Do communities exist? Complex patterns of overlapping marine species distributions - Rebecca Leaper; Piers K. Dunstan; Scott D. Foster; Neville S. Barrett; Graham J. Edgar (Ecology, 2014)
Understanding the way in which species are associated in communities is a fundamental question in ecology. Yet there remains a tension between communities as highly structured units or as coincidental collections of individualistic species. We explored these ideas using a new statistical approach that clusters species based on their environmental response: a species archetype, rather than clustering sites based on their species composition. We found groups of species that are consistently highly correlated, but that these groups are not unique to any set of locations and overlap spatially. The species present at a single site are a realization of species from the (multiple) archetype groups that are likely to be present at that location based on their response to the environment.

Looking for age-related growth decline in natural forests: unexpected biomass patterns from tree rings and simulated mortality - Jane R. Foster; Anthony W. D’Amato; John B. Bradford (Oecologia, 2014)

A Poisson–Gamma model for analysis of ecological non-negative continuous data - Scott D. Foster; Mark V. Bravington (Environmental and Ecological Statistics, 2013)

To mix or not to mix: comparing the predictive performance of mixture models vs. separate species distribution models - Francis K. C. Hui; David I. Warton; Scott D. Foster; Piers K. Dunstan (Ecology, 2013)
Species distribution models (SDMs) are an important tool for studying the patterns of species across environmental and geographic space. For community data, a common approach involves fitting an SDM to each species separately, although the large number of models makes interpretation difficult and fails to exploit any similarities between individual species responses. A recently proposed alternative that can potentially overcome these difficulties is species archetype models (SAMs), a model‐based approach that clusters species based on their environmental response. In this paper, we compare the predictive performance of SAMs against separate SDMs using a number of multi‐species data sets. Results show that SAMs improve model accuracy and discriminatory capacity compared to separate SDMs. This is achieved by borrowing strength from common species having higher information content. Moreover, the improvement increases as the species become rarer.

Reproductive success in a natural population of male three‐spined stickleback Gasterosteus aculeatus : effects of nuptial colour, parasites and body size - T. C. Sparkes; V. Rush; D. A. Kopp; S. A. Foster (Journal of Fish Biology, 2013)
The effects of nuptial colour, parasites and body size on reproductive success were examined in a natural population of three‐spined stickleback Gasterosteus aculeatus . Reproductive males were collected, with the contents of their nests, during the embryo‐guarding stage from Lynne Lake (Cook Inlet, Alaska, U.S.A.), and nuptial colour, infection status and body size were recorded. Regression analysis revealed that male body size was the only predictor, of those measured, of reproductive success in nature.

Viral infection of Phaeocystis globosa impedes release of chitinous star‐like structures: quantification using single cell approaches - A. R. Sheik; C. P. D. Brussaard; G. Lavik; R. A. Foster; N. Musat; B. Adam; M. M. M. Kuypers (Environmental Microbiology, 2013)
Summary Phaeocystis globosa is an ecologically important bloom‐forming phytoplankton, which sequesters substantial amounts of inorganic carbon and can form carbon‐enriched chitinous star‐like structures. Viruses infecting P. globosa (PgVs) play a significant regulatory role in population dynamics of the host species. However, the extent to which viruses alter host physiology and its carbon assimilation on single cell level is still largely unknown. This study demonstrates for the first time the impact of viral infection on carbon assimilation and cell morphology of individual axenic P. globosa cells using two single cell techniques: high resolution nanometre‐scale Secondary‐Ion Mass Spectrometry (nanoSIMS) approach and atomic force microscopy (AFM). Up until viral lysis (19 h post infection), the bulk carbon assimilation by infected P. globosa cultures was identical to the assimilation by the non‐infected cultures (33 µmol C l −1 ). However, single cell analysis showed that viral infection of P. globosa impedes the release of star‐like structures. Non‐infected cells transfer up to 44.5 µmol C l −1 (36%) of cellular biomass in the form of star‐like structures, suggesting a vital role in the survival of P. globosa cells. We hypothesize that impediment of star‐like structures in infected P. globosa cells may inactivate viral infectivity by forming flocculants after cell lysis. Moreover, we show that substantial amounts of newly produced viruses (∼ 68%) were attached to P. globosa cells prior to cell lysis. Further, we speculate that infected cells become more susceptible for grazing which provides potential reasons for the sudden disappearance of PgVs in the environment. The scenarios of enhanced grazing is at odds to the current perspective that viral infections facilitates microbial mediated processes by diverting host material away from the higher trophic levels.

Exercise-induced endocannabinoid signaling is modulated by intensity - David A. Raichlen; Adam D. Foster; Alexandre Seillier; Andrea Giuffrida; Gregory L. Gerdeman (European Journal of Applied Physiology, 2013)

Serum skeletal troponin I following inspiratory threshold loading in healthy young and middle-aged men - Glen E. Foster; Jiro Nakano; A. William Sheel; Jeremy A. Simpson; Jeremy D. Road; W. Darlene Reid (European Journal of Applied Physiology, 2012)

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)

Isolation and characterization of eight novel microsatellite loci in endangered Wyoming toad, Bufo baxteri - Renee M. Martin; Connie L. Keeler-Foster; Kenneth G. Boykin; Gerard Zegers; Wade D. Wilson (Conservation Genetics Resources, 2012)

The potential significance of the breaching of small farm dams in the Sneeuberg region, South Africa - John Boardman; Ian D. L. Foster (Journal of Soils and Sediments, 2011)

Groundwater use in developing cities: policy issues arising from current trends - Stephen D. Foster; Ricardo Hirata; Ken W. F. Howard (Hydrogeology Journal, 2011)

The synthetic triterpenoid CDDO-Imidazolide suppresses experimental liver metastasis - Jason L. Townson; Ian C. MacDonald; Karen T. Liby; Lisa Mackenzie; David W. Dales; Benjamin D. Hedley; Paula J. Foster; Michael B. Sporn; Ann F. Chambers (Clinical & Experimental Metastasis, 2011)

The potential for paleolimnology to determine historic sediment delivery to rivers - I. D. L. Foster; A. L. Collins; P. S. Naden; D. A. Sear; J. I. Jones; Y. Zhang (Journal of Paleolimnology, 2011)

Regional differences in awareness and attitudes regarding genetic testing for disease risk and ancestry - Charles R. Jonassaint; Eunice R. Santos; Crystal M. Glover; Perry W. Payne; Grace-Ann Fasaye; Nefertiti Oji-Njideka; Stanley Hooker; Wenndy Hernandez; Morris W. Foster; Rick A. Kittles; Charmaine D. Royal (Human Genetics, 2010)

A record of Holocene environmental and ecological changes from Wildwood Lake, Long Island, New York - W. Wyatt Oswald; David R. Foster; Elaine D. Doughty; Dana Macdonald (Journal of Quaternary Science, 2010)
Analyses of pollen, charcoal and organic content in a lake sediment core from Wildwood Lake, Long Island, New York, provide insights into the ecological and environmental history of this region. The early Holocene interval of the record (ca. 9800–8800 cal. a BP) indicates the presence of Pinus rigida – Quercus ilicifolia woodlands with high fire activity. A layer of sandy sediment dating to 9200 cal. a BP may reflect a brief period of reduced water depth, consistent with widespread evidence for cold, dry conditions at that time. Two other sandy layers, bracketed by 14 C dates, represent a sedimentary hiatus from ca. 8800 to 4500 cal. a BP. This discontinuity may reflect the removal of some sediment during brief periods of reduced water depth at 5300 and 4600 cal. a BP. In the upper portion of the record ( Quercus – Fagus – Carya forests and increasing abundance of Pinus rigida , perhaps due to reduced summer precipitation. Elevated percentages of herbaceous taxa in the uppermost sediments represent European agricultural activities. However, unlike charcoal records from southern New England, fire activity does not increase dramatically with European settlement. These findings indicate that present‐day Pinus rigida – Quercus ilicifolia woodlands on eastern Long Island are not a legacy of recent, anthropogenic disturbances. Copyright © 2010 John Wiley & Sons, Ltd.

Surface Water Concentrations and Loading Budgets of Pharmaceuticals and Other Domestic-Use Chemicals in an Urban Watershed (Washington, DC, USA) - Lirije Shala; Gregory D. Foster (Archives of Environmental Contamination and Toxicology, 2010)

Improving groundwater resource accounting in irrigated areas : a prerequisite for promoting sustainable use - S. S. D. Foster; C. J. Perry (Hydrogeology Journal, 2010)

A Mechanism for the induction of renal tumours in male Fischer 344 rats by short-chain chlorinated paraffins - Gayathri D. Warnasuriya; Barbara M. Elcombe; John R. Foster; Clifford R. Elcombe (Archives of Toxicology, 2010)

A record of Lateglacial and early Holocene environmental and ecological change from southwestern Connecticut, USA - W. Wyatt Oswald; David R. Foster; Elaine D. Doughty; Edward K. Faison (Journal of Quaternary Science, 2009)
Analyses of a sediment core from Highstead Swamp in southwestern Connecticut, USA, reveal Lateglacial and early Holocene ecological and hydrological changes. Lateglacial pollen assemblages are dominated by Picea and Pinus subg. Pinus , and the onset of the Younger Dryas (YD) cold interval is evidenced by higher abundance of Abies and Alnus viridis subsp. crispa . As climate warmed at the end of the YD, Picea and Abies declined and Pinus strobus became the dominant upland tree species. A shift from lacustrine sediment to organic peat at the YD–Holocene boundary suggests that the lake that existed in the basin during the Lateglacial interval developed into a swamp in response to reduced effective moisture. A change in wetland vegetation from Myrica gale to Alnus incana subsp. rugosa and Sphagnum is consistent with this interpretation of environmental changes at the beginning of the Holocene. Copyright © 2009 John Wiley & Sons, Ltd.

Patch size effects on plant species decline in an experimentally fragmented landscape - Cathy D. Collins; Robert D. Holt; Bryan L. Foster (Ecology, 2009)
Understanding local and global extinction is a fundamental objective of both basic and applied ecology. Island biogeography theory (IBT) and succession theory provide frameworks for understanding extinction in changing landscapes. We explore the relative contribution of fragment size vs. succession on species' declines by examining distributions of abundances for 18 plant species declining over time in an experimentally fragmented landscape in northeast Kansas, USA. If patch size effects dominate, early‐successional species should persist longer on large patches, but if successional processes dominate, the reverse should hold, because in our system woody plant colonization is accelerated on large patches. To compare the patterns in abundance among patch sizes, we characterize joint shifts in local abundance and occupancy with a new metric: rank occupancy–abundance profiles (ROAPs). As succession progressed, statistically significant patch size effects emerged for 11 of 18 species. More early‐successional species persisted longer on large patches, despite the fact that woody encroachment (succession) progressed faster in these patches. Clonal perennial species persisted longer on large patches compared to small patches. All species that persisted longer on small patches were annuals that recruit from the seed bank each year. The degree to which species declined in occupancy vs. abundance varied dramatically among species: some species declined first in occupancy, others remained widespread or even expanded their distribution, even as they declined in local abundance. Consequently, species exhibited various types of rarity as succession progressed. Understanding the effect of fragmentation on extinction trajectories requires a species‐by‐species approach encompassing both occupancy and local abundance. We propose that ROAPs provide a useful tool for comparing the distribution of local abundances among landscape types, years, and species.

Community‐level consequences of mycorrhizae depend on phosphorus availability - Cathy D. Collins; Bryan L. Foster (Ecology, 2009)
In grasslands, arbuscular mycorrhizal fungi (AMF) mediate plant diversity; whether AMF increase or decrease diversity depends on the relative mycotrophy in dominant vs. subordinate plants. In this study we investigated whether soil nutrient levels also influence the ability of AMF to mediate plant species coexistence. First, we developed a conceptual model that predicts the influence of AMF on diversity along a soil nutrient gradient for plant communities dominated by mycotrophic and non‐mycotrophic species. To test these predictions, we manipulated phosphorus to create a soil nutrient gradient for mesocosm communities composed of native prairie grasses and then compared community properties for mesocosms with and without AMF. We found that, where P was limiting, AMF increased plant diversity and productivity, and also altered community structure; however, at high P, AMF had little influence on aboveground communities. Compositional differences among treatments were due largely to a trade‐off in the relative abundance of C 3 vs. C 4 species. Our study emphasizes how environmental constraints on mutualisms may govern community‐ and ecosystem‐level properties.

An integrated lake-catchment approach for determining sediment source changes at Aqualate Mere, Central England - Nathan J. Pittam; Ian D. L. Foster; Tim M. Mighall (Journal of Paleolimnology, 2009)

Geochronology and provenance of the Late Paleozoic accretionary wedge and Gympie Terrane, New England Orogen, eastern Australia∗ - R. J. Korsch; C. J. Adams; L. P. Black; D. A. Foster; G. L. Fraser; C. G. Murray; C. Foudoulis; W. L. Griffin (Australian Journal of Earth Sciences, 2009)

Rapidity of responding to a hypoxic challenge during exercise - Blair D. Johnson; Trent Joseph; Glenn Wright; Rebecca A. Battista; Christopher Dodge; Alecia Balweg; Jos J. de Koning; Carl Foster (European Journal of Applied Physiology, 2009)

Stochastic and deterministic processes jointly structure tropical arthropod communities - M. D. Farnon Ellwood; Andrea Manica; William A. Foster (Ecology Letters, 2009)
The question of whether ecological assemblages are structured by stochastic and deterministic (e.g. interspecific competition) processes is controversial, but it is difficult to design sampling regimes and experiments that can dissect the relative importance of stochastic and deterministic processes in natural assemblages. Using null models, we tested communities of arthropod decomposers in tropical epiphytes for patterns of species co‐occurrence, while controlling for habitat gradients, seasonal variations and ecological succession. When environmental conditions were controlled, our analysis showed that the communities were structured stochastically. However, analysing mixed sets of communities that were deliberately created either from two distinct heights or two successional stages revealed that communities were structured deterministically. These results confirm that habitat gradients and dispersal/competition trade‐offs are capable of generating non‐random patterns within decomposer arthropod communities, but reveal that when such effects are accounted for, species co‐occurrence is fundamentally random.

Two distinct potato late blight resistance genes from Solanum berthaultii are located on chromosome 10 - Tae-Ho Park; Simon Foster; Gianinna Brigneti; Jonathan D. G. Jones (Euphytica, 2009)

Isolation of Three Diterpenoid Acids from Sunflowers, as Oviposition Stimulants for the Banded Sunflower Moth, Cochylis hospes - Bruce D. Morris; Laurence D. Charlet; Stephen P. Foster (Journal of Chemical Ecology, 2009)

Nature of the Weipa Bauxite deposit, northern Australia - G. Taylor; R. A. Eggleton; L. D. Foster; D. B. Tilley; M. Le Gleuher; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Regolith profile, mineralogy and geochemistry of the Weipa Bauxite, northern Australia - R. A. Eggleton; G. Taylor; M. Le Gleuher; L. D. Foster; D. B. Tilley; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Landscapes and regolith of Weipa, northern Australia - G. Taylor; R. A. Eggleton; L. D. Foster; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Phylogenetic diversity of cyanobacterial narB genes from various marine habitats - Ryan W. Paerl; Rachel A. Foster; Bethany D. Jenkins; Joseph P. Montoya; Jonathan P. Zehr (Environmental Microbiology, 2008)
Summary Nitrate, the most abundant combined, dissolved form of inorganic nitrogen in global oceans, is a common source of nitrogen (N) for phytoplankton including cyanobacteria. Using a nested polymerase chain reaction (PCR) method, the diversity of the cyanobacterial nitrate reductase gene, narB, was examined in plankton samples from a variety of marine habitats. A total of 480 narB gene fragment sequences were obtained from a coastal coral reef (Heron Island, Australia), open‐ocean tropical and subtropical oceanic waters (Atlantic and Pacific Oceans) and a temperate N. Pacific Ocean site (34°N, 129°W). Phylogenetic analyses distinguished eight picocyanobacterial narB clades comprised of DNA sequences derived from the nutrient‐replete coastal, nutrient‐deplete pelagic and tidally influenced coral reef habitats. The phylogeny of recovered narB gene sequences was consistent with 16S rRNA and ITS sequence phylogenies, suggesting minimal horizontal gene transfer of the narB gene. Depending on sampled habitat, environmental narB sequence types segregated into three divisions: non‐picocyanobacterial, coastal picocyanobacterial and open‐ocean picocyanobacterial sequences. Using a reverse transcription PCR method, narB mRNA sequences were amplified from Heron Island samples, indicating that narB expression can be detected in environmental samples.

Mineral magnetic signatures in a long core from Lake Qarun, Middle Egypt - I. D. L. Foster; F. Oldfield; R. J. Flower; K. Keatings (Journal of Paleolimnology, 2008)

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Using multiple archives to understand past and present climate–human–environment interactions: the lake Erhai catchment, Yunnan Province, China - J. A. Dearing; R. T. Jones; J. Shen; X. Yang; J. F. Boyle; G. C. Foster; D. S. Crook; M. J. D. Elvin (Journal of Paleolimnology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Timing and development of oroclines in the southern New England Orogen, New South Wales - R. Offler; D. A. Foster (Australian Journal of Earth Sciences, 2008)

Environmental tracers as indicators of karst conduits in groundwater in South Dakota, USA - Andrew J. Long; J. Foster Sawyer; Larry D. Putnam (Hydrogeology Journal, 2008)

Synthesis and pharmacological evaluation of m-terphenyl amines as cyclooxygenase inhibitors - John D. Bauer; Michael S. Foster; Jeffrey D. Hugdahl; Kristi L. Burns; Sheldon W. May; Stanley H. Pollock; Horace G. Cutler; Stephen J. Cutler (Medicinal Chemistry Research, 2007)

From introduction to fishery dominance: the initial impacts of the invasive carp Cyprinus carpio in Lake Naivasha, Kenya, 1999 to 2006 - J. R. Britton; R. R. Boar; J. Grey; J. Foster; J. Lugonzo; D. M. Harper (Journal of Fish Biology, 2007)
Following the accidental introduction of the carp Cyprinus carpio into Lake Naivasha during 1999, a sustainable population became rapidly established and in early 2004 became the principal species exploited in the commercial fishery. Over 9000 kg of carp were harvested from the lake between October 2005 and 2006, when fish were captured between fork lengths ( L F ) 200 and 800 mm (>8 kg). Diet of carp L F was dominated by zooplankton, >100 mm L F there was a shift to benthic macro‐invertebrates, with these carp feeding principally upon food resources previously unexploited by the fish community. Contrary to predictions and despite the increasing carp abundance, there has been macrophyte regeneration in littoral areas since 2004. There have been substantial increases in areal cover, with coverage in 2006 at levels not observed since the late 1980s, and significant increases in species richness. Possible reasons for this, and the significance of this carp introduction, are discussed.

Post‐glacial changes in spatial patterns of vegetation across southern New England - W. Wyatt Oswald; Edward K. Faison; David R. Foster; Elaine D. Doughty; Brian R. Hall; Barbara C. S. Hansen (Journal of Biogeography, 2007)
Aim We analysed lake‐sediment pollen records from eight sites in southern New England to address: (1) regional variation in ecological responses to post‐glacial climatic changes, (2) landscape‐scale vegetational heterogeneity at different times in the past, and (3) environmental and ecological controls on spatial patterns of vegetation. Location The eight study sites are located in southern New England in the states of Massachusetts and Connecticut. The sites span a climatic and vegetational gradient from the lowland areas of eastern Massachusetts and Connecticut to the uplands of north‐central and western Massachusetts. Tsuga canadensis and Fagus grandifolia are abundant in the upland area, while Quercus , Carya and Pinus species have higher abundances in the lowlands. Methods We collected sediment cores from three lakes in eastern and north‐central Massachusetts (Berry East, Blood and Little Royalston Ponds). Pollen records from those sites were compared with previously published pollen data from five other sites. Multivariate data analysis (non‐metric multi‐dimensional scaling) was used to compare the pollen spectra of these sites through time. Results Our analyses revealed a sequence of vegetational responses to climate changes occurring across southern New England during the past 14,000 calibrated radiocarbon years before present (cal yr bp ). Pollen assemblages at all sites were dominated by Picea and Pinus banksiana between 14,000 and 11,500 cal yr bp ; by Pinus strobus from 11,500 to 10,500 cal yr bp ; and by P. strobus and Tsuga between 10,500 and 9500 cal yr bp . At 9500–8000 cal yr bp , however, vegetation composition began to differentiate between lowland and upland sites. Lowland sites had higher percentages of Quercus pollen, whereas Tsuga abundance was higher at the upland sites. This spatial heterogeneity strengthened between 8000 and 5500 cal yr bp , when Fagus became abundant in the uplands and Quercus pollen percentages increased further in the lowland records. The differentiation of upland and lowland vegetation zones remained strong during the mid‐Holocene Tsuga decline (5500–3500 cal yr bp ), but the pattern weakened during the late‐Holocene (3500–300 cal yr bp ) and European‐settlement intervals. Within‐group similarity declined in response to the uneven late‐Holocene expansion of Castanea , while between‐group similarity increased due to homogenization of the regional vegetation by forest clearance and ongoing disturbances. Main conclusions The regional gradient of vegetation composition across southern New England was first established between 9500 and 8000 cal yr bp . The spatial heterogeneity of the vegetation may have arisen at that time in response to the development or strengthening of the regional climatic gradient. Alternatively, the differentiation of upland and lowland vegetation types may have occurred as the climate ameliorated and an increasing number of species arrived in the region, arranging themselves in progressively more complex vegetation patterns across relatively stationary environmental gradients. The emergence of a regional vegetational gradient in southern New England may be a manifestation of the increasing number of species and more finely divided resource gradient.

Influence of the Amazon River plume on distributions of free‐living and symbiotic cyanobacteria in the western tropical north Atlantic Ocean - R. A. Foster; A. Subramaniam; C. Mahaffey; E. J. Carpenter; D. G. Capone; J. P. Zehr (Limnology and Oceanography, 2007)
The vertical and horizontal distributions of seven diazotrophic populations in the western tropical north Atlantic (WTNA) Ocean were examined using a nifH DNA quantitative polymerase chain reaction (QPCR) approach. The nifH phylotype abundances were highest near the surface and decreased with depth, with the exception of the cyanobacterial symbiont Calothrix , which was not detected at any station. Richelia associated with the diatoms Rhizosolenia clevei and Hemiaulus hauckii were distributed within the freshwater lens of the Amazon plume. Abundances of H. hauckii ‐ Richelia nifH genes dominated all depths in 6 of 10 vertical profiles and 10 of 20 surface samples. In addition, estimates of Richelia associated with H. hauckii increased northwest (8‐ 12°N, 56‐54°W) from the river mouth, where significantly ( p 10 5 copies L −1 ) were found in mesohaline waters (31‐34.9). nifH copy abundance for surface populations of the H. hauckii‐Richelia symbioses were positively correlated ( r 2 = 0.59) with salinity. Three unicellular cyanobacterial groups and Trichodesmium had similar horizontal distributions, where the highest nifH copy estimates were at stations with salinity ≥35 and northeast (6‐10°N 50°W) of the freshwater lens. The abundance of Trichodesmium spp. and unicellular Group B nifH gene copies co‐varied ( r 2 = 0.60). The QPCR study showed the dominance of H. hauckii‐Richelia symbioses in the Amazon plume waters, implying that these associations had an ecological advantage over the other diazotrophs. Outside of the plume nutrients were below detection, abundances of freeliving unicellular cyanobacterial phylotypes, including a novel group designated Group C, were abundant (>10 5 copies L −1 ) and comparable to the abundances of Trichodesmium spp. Thus, there appeared to be a cascade of diazotrophic communities along gradients of salinity and nutrients in the WTNA.

EphB3 receptor and ligand expression in the adult rat brain - Christopher A. Willson; Roy D. Foster; Stephen M. Onifer; Scott R. Whittemore; Jorge D. Miranda (Journal of Molecular Histology, 2006)

Post-depositional 137Cs Mobility in the Sediments of Three Shallow Coastal Lagoons, SW England - I. D. L. Foster; T. M. Mighall; H. Proffitt; D. E. Walling; P. N. Owens (Journal of Paleolimnology, 2006)

The Definition of British Water Beetle Species Pools (Coleoptera) and their Relationship to Altitude, Temperature, Precipitation and Land Cover Variables - M. D. Eyre; G. N. Foster; M. L. Luff; S. P. Rushton (Hydrobiologia, 2006)

At least one YMHCI molecule in the chicken is alloimmunogenic and dynamically expressed on spleen cells during development - Henry D. Hunt; Ronald M. Goto; Douglas N. Foster; Larry D. Bacon; Marcia M. Miller (Immunogenetics, 2006)

Modelling the spread of scrapie in a sheep flock: evidence for increased transmission during lambing seasons - S. Touzeau; M. E. Chase-Topping; L. Matthews; D. Lajous; F. Eychenne; N. Hunter; J. D. Foster; G. Simm; J.-M. Elsen; M. E. J. Woolhouse (Archives of Virology, 2006)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Character and distribution of exposed glaciodeltaic deposits off outer Cape Cod, Massachusetts, and their effects on hydrogeology and benthic habitats - L. J. Poppe; D. S. Foster; W. W. Danforth (Geo-Marine Letters, 2006)

Use of optical density as a measure of Claviceps africana conidial suspension concentration - D. J. Herde; M. J. Ryley; S. D. Foster; V. J. Galea; R. G. Henzell; D. R. Jordan (Australasian Plant Pathology, 2006)

Carbon monoxide levels at a toll plaza near Durban, South Africa - R. D. Diab; S. J. Foster; K. François; B. S. Martincigh; L. F. Salter (Environmental Chemistry Letters, 2005)

Impedance-gradient electrode reduces skin irritation induced by transthoracic defibrillation - P. F. Meyer; P. D. Gadsby; D. Van Sickle; W. E. Schoenlein; K. S. Foster; G. P. Graber (Medical & Biological Engineering & Computing, 2005)

Comparative Aquatic Toxicity Evaluation of 2-(Thiocyanomethylthio)benzothiazole and Selected Degradation Products Using Ceriodaphnia dubia - S. T. Nawrocki; K. D. Drake; C. F. Watson; G. D. Foster; K. J. Maier (Archives of Environmental Contamination and Toxicology, 2005)

Identification Of Sex Pheromone Components Of The Painted Apple Moth: A Tussock Moth With A Thermally Labile Pheromone Component - A. M. El-Sayed; A. R. Gibb; D. M. Suckling; B. Bunn; S. Fielder; D. Comeskey; L. A. Manning; S. P. Foster; B. D. Morris; T. ando; K. Mori (Journal of Chemical Ecology, 2005)

Influence of Targets and Assessment Region Size on Perceived Conservation Priorities - David D. Diamond; C. Diane True; Taisia M. Gordon; Scott P. Sowa; Walter E. Foster; K. Bruce Jones (Environmental Management, 2005)

Heat-shock proteins and their role in chondrocyte protection, an application for autologous transplantation - D. A. Sawatzky; R. Foster; M. P. Seed; D. A. Willoughby (Inflammopharmacology, 2005)

Exploring the relationship between land cover and the distribution of water beetle species (Coleoptera) at the regional scale - M. D. Eyre; G. N. Foster; M. L. Luff (Hydrobiologia, 2005)

ISOLATION OF THE DITERPENOIDS, ENT-KAURAN-16?-OL AND ENT-ATISAN-16?-OL, FROM SUNFLOWERS, AS OVIPOSITION STIMULANTS FOR THE BANDED SUNFLOWER MOTH, Cochylis hospes - BRUCE D. MORRIS; STEPHEN P. FOSTER; SHARON GRUGEL; LAURENCE D. CHARLET (Journal of Chemical Ecology, 2005)

The new plant virus family Flexiviridae and assessment of molecular criteria for species demarcation - M. J. Adams; J. F. Antoniw; M. Bar-Joseph; A. A. Brunt; T. Candresse; G. D. Foster; G. P. Martelli; R. G. Milne; S. K. Zavriev; C. M. Fauquet (Archives of Virology, 2004)

Long‐Term Population Changes of Native and Introduced Birds in the Alaka‘i Swamp, Kaua‘i - JEFFREY T. FOSTER; ERIK J. TWEED; RICHARD J. CAMP; BETHANY L. WOODWORTH; COREY D. ADLER; TOM TELFER (Conservation Biology, 2004)
Within the last 30 years, five endemic bird species of the Alaka‘i Swamp, Kaua‘i, Hawai‘i, have likely gone extinct. We documented population trends of the remaining avifauna in this time period to identify a common pattern in the Hawaiian Islands: decline of native species and expansion of introduced species. We conducted bird surveys over 100 km 2 of the Alaka‘i and Kōke‘e regions of Kaua‘i in March–April 2000 to estimate population size, distribution, and range limits of seven native and six introduced forest birds. We compared the results with four previous surveys conducted over the last 30 years. Five of the seven native species we studied have fared well, maintaining sizeable populations (>20,000 individuals) and unchanged or increasing numbers. The endemic ‘Akikiki ( Oreomystis bairdi ), however, declined from 6296 (SE ± 1374) to 1472 (SE ± 680) individuals and exhibited range contraction from 88 to 36 km 2 . The ‘I‘iwi ( Vestiaria coccinea ) also experienced a decline and contraction, though not as severe. Populations of several introduced forest birds are increasing, but all species, excluding the Japanese White‐eye ( Zosterops japonicus ), were at low numbers ( Cettia diphone ) recently invaded, whereas another, the Red‐billed Leiothrix ( Leiothrix lutea ), has been extirpated. Two hurricanes in the past 20 years appear to have most strongly affected nectarivores and may have contributed to the decline or extinction of several other species. Overall, native bird populations on Kaua‘i have exhibited species‐specific responses to limiting factors. Although most native populations appear stable, the extant native avifauna is vulnerable as a result of limited distributions and the potential for widespread habitat degradation.

Virology Division News: The new plant virus family Flexiviridae and assessment of molecular criteria for species demarcation - M. J. Adams; J. F. Antoniw; M. Bar-Joseph; A. A. Brunt; T. Candresse; G. D. Foster; G. P. Martelli; R. G. Milne; C. M. Fauquet (Archives of Virology, 2004)

Downstream of downtown: urban wastewater as groundwater recharge - S. S. D. Foster; P. J. Chilton (Hydrogeology Journal, 2004)

Long-Term Soil Accumulation of Chromium, Copper, and Arsenic Adjacent to Preservative-Treated Wood - S. Lebow; D. Foster; J. Evans (Bulletin of Environmental Contamination and Toxicology, 2004)

An investigation into the relationship between water beetle (Coleoptera) distribution and land cover in Scotland and northeast England - M. D. Eyre; G. N. Foster; M. L. Luff; J. R. Staley (Journal of Biogeography, 2003)
Aims To determine the relationship between satellite‐derived land cover data and distribution patterns of water beetle species pools. Location A total of 687 British national grid 10 km squares in Scotland and 588 1 km grid squares in 99 10 km grid squares in northeast England. Methods Multivariate classification and constrained ordination analyses were used with water beetle species and land cover data. Results The major variation in both the Scotland and northeast England 10 km species pools was from squares with upland acid water habitats to squares with lowland fens and ponds whilst for the 1 km northeast England data it was from squares dominated by fast‐flowing streams and rivers to those with fens and ponds. The secondary variations in the 10 and 1 km analyses were the primary ones juxtaposed. Constrained ordination of the Scottish 10 km data showed upland land cover types to be most influential in determining species pool distribution whilst lowland covers were more important with both the 10 and 1 km northeast England pools. The three analyses showed that coastal cover had a relatively high influence on species pool distribution but no species pool group was dominated by coastal species. Main conclusions There were strong relationships between water beetle species pool distributions and the satellite‐derived land cover types dominating upland and lowland areas. The major variation in the northeast England species pool data differed at the two scales analysed. Results indicated that there is considerable potential for the synthesis of water beetle distribution and land cover data for use in environmental and conservation monitoring at both the regional and national scales.

Increase in synthesis of human monoclonal antibodies by transfected Sp2/0 myeloma mouse cell line under conditions of microgravity - L.J.R. Foster; D. Catzel; S. Atwa; M. Zarka; S.M. Mahler (Biotechnology Letters, 2003)

Changing suspended sediment and particulate phosphorus loads and pathways in underdrained lowland agricultural catchments; Herefordshire and Worcestershire, U.K. - I. D. L. Foster; A. S. Chapman; R. M. Hodgkinson; A. R. Jones; J. A. Lees; S. E. Turner; M. Scott (Hydrobiologia, 2003)

Enhanced hydantoinase and N-carbamoylase activity on immobilisation of Agrobacterium tumefaciens - Ingrid M. Foster; Rosemary D. Dorrington; Stephanie G. Burton (Biotechnology Letters, 2003)

Fire on the New England landscape: regional and temporal variation, cultural and environmental controls - T. Parshall; D. R. Foster (Journal of Biogeography, 2002)
Aim We use a retrospective approach to reconstruct the past distribution of fire in New England and to investigate the important drivers of this pattern across the period of European arrival to North America. Location Our study sites are in New England, and range from pitch pine and oak forests of coastal Massachusetts, pine and hardwood forests of central Massachusetts, and northern hardwood and spruce fir forests of northern Massachusetts and Vermont. Methods We collected sediment profiles from eighteen lakes across the study area to assess fossil charcoal and pollen abundance over the past 1000 years, including the time period of European arrival and settlement. Results Based on presettlement pollen composition, our study sites are divided into three vegetation types: (1) pitch pine and oak, (2) oak, pine and hardwood and (3) northern hardwoods. The abundance of presettlement charcoal in these lakes is closely related to climate and the composition of surrounding vegetation. Charcoal is most abundant in pitch pine forests and least common in northern hardwood forests. Following the arrival of Europeans, charcoal abundance increased at most sites substantially, and vegetation composition changed in a direction of either greater dominance by pitch pine or white pine, depending on whether the forests were located in the southern or northern part of New England. Main conclusions The major factor influencing the distribution of fire across New England is climate, which has a direct effect on the physical conditions conducive to fire ignition and spread and an indirect effect on fire through its control on the distribution of vegetation at this spatial scale. We find evidence that other factors exert some control over local fire regimes as well including landforms and their impact on vegetation composition, firebreaks and prevailing winds. Native Americans likely influenced the local occurrence of fire, but their impact on regional fire regimes in New England is not apparent from this or other studies. However, additional palaeoecological, archaeological and historical work needs to be carried out to better address this question. In contrast, Europeans had a dramatic effect on fire throughout the New England landscape, increasing its occurrence almost everywhere.

A constitutive gene expression system derived from the tCUP cryptic promoter elements - K. Malik; K. Wu; X.-Q. Li; T. Martin-Heller; M. Hu; E. Foster; L. Tian; C. Wang; K. Ward; M. Jordan; D. Brown; S. Gleddie; et al. (Theoretical and Applied Genetics, 2002)

Island theory, matrix effects and species richness patterns in habitat fragments - William M. Cook; Kurt T Lane; Bryan L. Foster; Robert D. Holt (Ecology Letters, 2002)
Island biogeography theory, created initially to study diversity patterns on islands, is often applied to habitat fragments. A key but largely untested assumption of this application of theory is that landscape matrix species composition is non‐overlapping with that of the islands. We tested this assumption in successional old field patches in a closely mowed matrix, and because our patches are appropriately viewed as sets of contiguous habitat units we studied patterns of species richness per unit area. Previous studies at our site did not find that diversity patterns on patch ‘islands’ conformed to predictions of island biogeography theory. Our results indicate that when matrix species are removed from the patch samples, diversity patterns conform better to theory. We suggest that classical island theory remains an appropriate tool to study diversity patterns in fragmented habitats, but that allowances should be made for spill‐over colonization of ‘islands’ from the ‘sea’.

Clonal mixing in the soldier‐producing aphid Pemphigus spyrothecae (Hemiptera: Aphididae) - Paul C. D. Johnson; John A. Whitfield; William A. Foster; William Amos (Molecular Ecology, 2002)
Illuminating the genetic relationships within soldier‐producing aphid colonies is an essential element of any attempt to explain the evolution of the altruistic soldier caste. Pemphigus spyrothecae is a soldier‐producing aphid that induces galls on the leaf petioles of its host (trees of the genus Populus ). At least a quarter of the aphids within the clonally produced gall population are morphologically and behaviourally distinct first‐instar soldiers that defend the gall population from predation. Using field trapping and microsatellites, we investigated the degree of clonal mixing within natural gall populations. Field trapping in the UK showed that all the migrants of P. spyrothecae and of two other Pemphigus species were wingless first‐instar soldiers. The average degree of mixing estimated from trapping P. spyrothecae migrants was 0.68% (range = 0–15%). Microsatellite genotyping of 277 aphids from 13 galls collected in Italy revealed an average mixing level of 10.4% (range = 0–59%). Six galls contained more than one clone (range = 2–5 clones). Non‐kin aphids were not restricted to the soldier caste but were evenly distributed across instars. An additional gall, from which 527 occupants were genotyped, contained 12 non‐kin aphids distributed among nine clones, showing that clonal diversity can be high even when mixing is very low. These observations suggest that although soldiers migrate regularly and can moult and reproduce within foreign galls, clonal mixing in this species is generally low and is unlikely to provide a barrier to the evolution of investment by the aphid clones in an altruistic soldier caste.

Bioaccumulation of PCBs in Aquatic Biota from a Tidal Freshwater Marsh Ecosystem - B. S. Crimmins; P. Doelling Brown; D. P. Kelso; G. D. Foster (Archives of Environmental Contamination and Toxicology, 2002)

Molecular evidence that the aphid-transmitted Tomato mild mottle virus belongs to the Potyviridae family but not the Potyvirus genus - W. A. Monger; N. J. Spence; G. D. Foster (Archives of Virology, 2001)

Analysis of candidate antagonists of IAP-mediated caspase inhibition using yeast reconstituted with the mammalian Apaf-1-activated apoptosis mechanism - C. J. Hawkins; J. Silke; A. M. Verhagen; R. Foster; P. G. Ekert; D. M. Ashley (Apoptosis, 2001)

Enhancers and core promoter elements are essential for the activity of a cryptic gene activation sequence from tobacco, tCUP - K. Wu; K. Malik; L. Tian; M. Hu; T. Martin; E. Foster; D. Brown; B. Miki (Molecular Genetics and Genomics, 2001)

Characterisation of a Tobamovirus from Trailing Petunias - Nicola J. Spence; Ian Sealy; Peter R. Mills; Gary D. Foster (European Journal of Plant Pathology, 2001)

Molecular Identification of Oat Mosaic Virus as a Bymovirus - Wendy A. Monger; Gerard R.G. Clover; Gary D. Foster (European Journal of Plant Pathology, 2001)

Statistical Analysis of Spatial Pattern: A Comparison of Grid and Hierarchical Sampling Approaches - R. G. Cole; T. R. Healy; M. L. Wood; D. M. Foster (Environmental Monitoring and Assessment, 2001)

Population dynamics of a scrapie outbreak - L. Matthews; P. G. Coen; J. D. Foster; N. Hunter; M. E. J. Woolhouse (Archives of Virology, 2001)

Expression of endothelin receptor subtypes and their messenger RNAs in diabetic rat prostate: Effect of insulin treatment - Motoaki Saito; Yoshihiro Wado; Kazuyoshi Ikeda; ZeJing Wang; Harris E. Foster; Shannon D. Smith; Robert M. Weiss; Jamshid Latifpour (Molecular and Cellular Biochemistry, 2000)

Molecular characterization of a new member of the immunoglobulin superfamily that potentially functions in T-cell activation and development - D. M. Ruble; D. N. Foster (Immunogenetics, 2000)

Identification of 1-Octacosanal and 6-Methoxy-2-Benzoxazolinone from Wheat as Ovipositional Stimulants for Hessian Fly, Mayetiola destructor - Bruce D. Morris; Stephen P. Foster; Marion O. Harris (Journal of Chemical Ecology, 2000)

An Isolated In-Situ Rat Head Perfusion Model for Pharmacokinetic Studies - Kelley A. Foster; George D. Mellick; Michael Weiss; Michael S. Roberts (Pharmaceutical Research, 2000)

Seasonal Changes and Tissue Distribution of Mercury in Largemouth Bass ( Micropterus salmoides ) from Dorena Reservoir, Oregon - E. P. Foster; D. L. Drake; G. DiDomenico (Archives of Environmental Contamination and Toxicology, 2000)

Codon optimization, genetic insulation, and an rtTA reporter improve performance of the tetracycline switch - Kevin D. Wells; Juli A. Foster; Karen Moore; Vernon G. Pursel; Robert J. Wall (Transgenic Research, 1999)

Analysis of a translational enhancer present within the 5′-terminal sequence of the genomic RNA of potato virus S - R. L. Turner; M. Glynn; S. C. Taylor; M.-K. Cheung; C. Spurr; D. Twell; G. D. Foster (Archives of Virology, 1999)

A Historical Perspective on Pitch PineScrub Oak Communities in the Connecticut Valley of Massachusetts - G. Motzkin; W. A. Patterson III; D. R. Foster (Ecosystems, 1999)

Tissue-Specific Fatty Acid Composition of Glandular Trichomes of Mite-Resistant and -Susceptible Pelargonium xhortorum - R. A. Grazzini; P. R. Paul; T. Hage; D. L. Cox-Foster; J. I. Medford; R. Craig; R. O. Mumma (Journal of Chemical Ecology, 1999)

Polychlorinated Dibenzo-p-dioxin and Polychlorinated Dibenzofuran Congener Profiles in Fish, Crayfish, and Sediment Collected near a Wood Treating Facility and a Bleached Kraft Pulp Mill - E. P. Foster; D. Drake; R. Farlow (Bulletin of Environmental Contamination and Toxicology, 1999)

Soil carbon and nitrogen in a pine-oak sand plain in central Massachusetts: Role of vegetation and land-use history - Jana E. Compton; Richard D. Boone; Glenn Motzkin; David R. Foster (Oecologia, 1998)

Distribution of aquatic macroinvertebrates within peatland pool complexes in the Flow Country, Scotland - I. S. Downie; J. C. Coulson; G. N. Foster; D. P. Whitfield (Hydrobiologia, 1998)

The communicative meaning of body oscillations in the social wasp, Polistes fuscatus (Hymenoptera, Vespidae) - J. L. Savoyard; G. J. Gamboa; D. L. D. Cummings; R. L. Foster (Insectes Sociaux, 1998)

Effects of gravidity on habitat use and antipredator behaviour in three‐spined sticklebacks - A. D. Rodewald; S. A. Foster† (Journal of Fish Biology, 1998)
Habitat use was examined in six Alaskan populations of three‐spined sticklebacks Gasterosteus aculeatus . In three lakes with predatory fishes, gravid female sticklebacks remained closer to refuge than did non‐gravid females, while those in lakes devoid of piscivores did not display this shift in behaviour. Gravid females in a lake with predatory rainbow trout Oncorhynchus mykiss used different evasive manoeuvres than did non‐gravid females during in situ encounters with a model rainbow trout. Gravid females were more likely to incorporate a protean element in their flight moffements than were non‐gravid females. Offerall, these data suggest that gravid female three‐spined sticklebacks modify habitat use and escape behaviour to reduce vulnerability to predators.

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

History and Importance of Land Use and Protection in the North Quabbin Region of Massachusetts (USA) - Alisa D. Golodetz; David R. Foster (Conservation Biology, 1997)
Evaluating the consequences and future of land protection requires broad temporal and spatial perspectives of ecological and cultural factors. We assessed the development of a system of protected areas comprising 37% of central Massachusetts in terms of changing rates and means of land protection. We compared protected areas to the surrounding matrix in terms of physical, biological, and historical features and used these results to raise issues concerning future planning. The rate, purpose, and means of land protection in the North Quabbin Region (168,312 ha) have been dynamic as a result of changes in cultural values and transformation of the landscape from predominantly agriculture to forest. Protected lands are managed by 25 federal and state agencies, private groups, and municipal departments and commissions and are physically and biologically typical of the regional landscape which results from (1) participation of diverse organizations with varied agendas; (2) predominance of large government acquisitions driven by landscape‐scale criteria; and (3) absence of coordination among groups. The large area, relative homogeneity and largely undeveloped status of the North Quabbin Region suggest conservation goals distinct from those in the fragmented and extensively developed neighboring areas of the Connecticut River Valley and Cape Cod and Islands Region. Large tracts of forests, wetlands, and lakes in the North Quabbin Region provide (1) habitat for species requiring extensive, intact areas; (2) the opportunity to maintain broad‐scale ecological processes; (3) connections to regional conservation areas; and (4) recreation. To realize the area’s potential, a comprehensive plan must be based on a broad‐scale perspective and historical understanding of the landscape.

Trends in Genetic and Environmental Parameters for Height, Diameter, and Volume in a Multilocation Clonal Study with Loblolly Pine - A. D. Paul; G. S. Foster; T. Caldwell; J. McRae (Forest Science, 1997)
Seedlings from 30 full-sib families (contained in 2, 4 x 4 factorials) of loblolly pine (Pinus taeda L.) were cloned and planted in three test sites in Georgia. Analyses were conducted on total height at ages 1 to 5 yr in the field, dbh at age 5, and individual tree volume at age 5. Four sources of genetic control were tested: male parent, female parent, male x female parent interaction, and clone within family. Differential growth responses due to test sites were present. Significant differences were detected among male parents for only one (age 5 height) of the seven traits in only one factorial. However, variation for height among female parents was found at ages 1 to 5 in only one of the two factorials accounting for 1% to 9% of the total variation. Significant effects of clone within family were found at all ages in one factorial and at ages 1, 3, and 4 in the other factorial for height but not for dbh or individual tree volume. None of the parental sources (male, female, or male x female) were interactive with test sites except one isolated case at age 2 in one factorial. However, the clone within family source of variation interacted significantly with site for height at ages 3 to 5 in factorial 1. Differences due to male or female parent effects were somewhat lower than has been found in other similar studies, possibly due to the relatively low number of parents in both factorials and hence, sampling effects. Future genetic studies should include more parents in the mating design but with approximately the same number of cloned individuals per cross in order to provide a better test of sources of variation. Trends in genetic and environmental variances and heritabilities were examined. Additive genetic variance (VA')for tree height displayed a steady increase from age 1 to 5. Dominance genetic variance (VD') for height also increased steadily over the same age range. The relationship between VA' and VD' differed between the two factorials. In factorial 1, VA' was larger than VD' for ages 1 to 4, then VD' became larger for age 5. The reverse pattern occurred in factorial 2. Epistatic genetic variance was detected only at age 1 for height in factorial 1 and at ages 1 and 3 in factorial 2. Dominance variance equaled or exceeded additive genetic variance for dbh and individual tree volume at age 5. Narrow-sense and broad-sense heritabilities for height were low to intermediate (0.05 to 0.37) from ages 1 to 5 and were more or less stable over ages. The importance of dominance genetic variance, at least to age 5, underscores the likelihood of additional genetic gains through a clonal tree improvement and deployment program beyond the gains achieved in a seed orchard/seedling based program. For. Sci. 42(1):87-98.

A CaMV 35S promoter driven cDNA clone of tobacco mosaic virus can infect host plant tissue despite being uninfectious when manually inoculated onto leaves - E. M. Dagless; M. H. Shintaku; R. S. Nelson; G. D. Foster (Archives of Virology, 1997)

Deletion analysis of a translational enhancer upstream from the coat protein open reading frame of potato virus S - R. Turner; G. D. Foster (Archives of Virology, 1997)

Natural scrapie in a closed flock of Cheviot sheep occurs only in specific PrP genotypes - N. Hunter; J. D. Foster; W. Goldmann; M. J. Stear; J. Hope; C. Bostock (Archives of Virology, 1996)

The effect of elevated intracranial pressure on the vibrational response of the ovine head - Milan Stevanovic; George R. Wodicka; Joe D. Bourland; George P. Graber; Kirk S. Foster; Gary C. Lantz; Willis A. Tacker; Allen Cymerman (Annals of Biomedical Engineering, 1995)

Analysis of a translational enhancer upstream from the coat protein open reading frame of potato virus S - R. Turner; N. Bate; D. Twell; G. D. Foster (Archives of Virology, 1994)

In vivo characterisation of a translational enhancer upstream from the coat protein open reading frame of potato virus S - R. Turner; N. Bate; D. Twell; G. D. Foster (Archives of Virology, 1994)

Almost equivalence of combinatorial and distance processes for discrimination in multielement images - M. Ferraro; D. H. Foster (Biological Cybernetics, 1991)

Bootstrap variance estimators for the parameters of small-sample sensory-performance functions - D. H. Foster; W. F. Bischof (Biological Cybernetics, 1987)

Some observations onStrongwellsea castrans [Zygomycetes: Entomophthorales], a parasite of root flies [Delia spp.], in the south of Scotland - D. J. Lamb; G. N. Foster (BioControl, 1986)

Osmotic adjustment in cyanobacteria from hypersaline environments - R. H. Reed; J. A. Chudek; R. Foster; W. D. P. Stewart (Archives of Microbiology, 1984)